Biaxially stretched film, laminate, and eco-friendly packaging material comprising the film
Patent Information
- Application Number
- JP2024198612
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-05-14
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-04-11
AI Technical Summary
【0018】 本発明による二軸延伸フィルムは、ポリ乳酸(PLA)およびポリヒドロキシアルカノエート(PHA)を含み、特定含有量範囲のPHAを含み、フィルムの柔軟騒音複合指数(LSN)が特定の範囲を満足することにより、優れた強度および柔軟性を同時に有するとともに、騒音度が低く、光学特性および熱的特性が向上し得る。
Smart Images

Figure 2025032119000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to biaxially oriented films, laminates, and environmentally conscious packaging materials comprising the films. [Background technology]
[0002] Recently, the use of disposable products has increased due to the so-called untact consumption culture and hygiene concerns, and the use of disposable products, especially food packaging materials, has been increasing significantly.
[0003] Currently, the general-purpose plastic films used for packaging materials include polyvinyl chloride (PVC), polyethylene (PE), and polypropylene (PP), which are derived from petroleum. However, PVC film is subject to many restrictions due to the generation of harmful substances such as dioxins when incinerated, and polyethylene film has poor dimensional stability and low mechanical properties, so its use is limited to low-grade packaging paper. Polypropylene film is a film that forms a relatively stable molecular structure and has good mechanical properties, but after use in packaging applications, it is mostly disposed of in landfills, which causes serious environmental problems as a cause of soil pollution due to the characteristics of plastic film that accumulate without decomposing due to its chemical and biological stability.
[0004] Recently, much research has been conducted on polylactic acid (PLA), an aliphatic polyester whose resin itself is highly biodegradable. However, the polylactic acid film is not flexible enough and is noisy, so its use for packaging is limited.
[0005] Therefore, research is being conducted on films using polylactic acid mixed with other resins.
[0006] For example, Patent Document 1 discloses a film using a mixture of polylactic acid and polybutyleneadipate terephthalate (PBAT). However, in this case, there may be problems in that the compatibility between the two materials is insufficient, resulting in reduced transparency, reduced thermal properties, and difficulty in simultaneously achieving satisfactory flexibility and strength.
[0007] Research has also been conducted on multilayer films in which a resin layer containing polylactic acid is laminated with another resin layer such as polytriethylene terephthalate (PTT), etc. However, in this case, not only is it difficult to achieve a satisfactory noise reduction effect or flexibility, but there may also be problems in that the compatibility between the resin layers decreases, leading to poor interlayer adhesion properties or detachment from each other, adversely affecting processability and productivity. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Korean Patent Publication No. 2014-0106882 Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention has been devised to solve the problems of the prior art mentioned above. An object of the present invention is to provide a biaxially oriented film which simultaneously has excellent strength and flexibility, has excellent compatibility between resins, has excellent transparency, and has improved noise level and thermal properties.
[0010] Another object of the present invention is to provide a laminate which simultaneously has excellent strength and flexibility, improved noise and thermal properties, and excellent interlayer adhesion properties due to good interlayer compatibility between the first and second layers.
[0011] It is still another object of the present invention to provide a method for producing a laminate which is excellent in processability and productivity and can achieve the above-mentioned properties by an economical and efficient method.
[0012] It is still another object of the present invention to provide a high-quality, environmentally friendly packaging material which is biodegradable and environmentally friendly by using a biaxially oriented film or laminate having the above-mentioned properties. [Means for solving the problem]
[0013] The present invention provides a biaxially stretched film that contains polylactic acid (PLA) and polyhydroxyalkanoate (PHA), and that contains more than 0% by weight and less than 30% by weight of polyhydroxyalkanoate (PHA) based on the total weight of the biaxially stretched film, and when the film has a thickness of 19 to 21 μm, has a flexible noise composite index (LSN) represented by the following formula 1-1 of 20 or less.
[0014] <Formula 1-1> Flexible noise composite index (LSN) = N AVG ×LS In the above formula 1-1, N AVG is the average sound level (dB) calculated by measuring the maximum sound level five times when a class 2 sound level meter specified in KS C IEC61672-1 is aimed toward the noise source and a biaxially stretched film test piece with a width of 21 cm and a length of 29.5 cm is swung at a speed of 120 times per minute at a point 1.2m to 1.5m above the ground. The unit is omitted. The LS is a unit-free value that indicates the loop stiffness (gf) measured by fixing a loop-shaped biaxially stretched film specimen having a width of 1.5 cm and a length of 18 cm to a loop stiffness tester and measuring the load at the center of the loop based on ASTM D747.
[0015] The present invention also provides a laminate comprising a first layer comprising a first polylactic acid (PLA) and a polyhydroxyalkanoate (PHA), and a second layer disposed on one side of the first layer and comprising a second polylactic acid (PLA), the first layer comprising more than 0% by weight and less than 30% by weight of polyhydroxyalkanoate (PHA) based on the total weight of the first layer.
[0016] The present invention also provides a method for producing a laminate, the method comprising the steps of: preparing a first resin including a first polylactic acid (PLA) and a polyhydroxyalkanoate (PHA), and a second resin including a second polylactic acid (PLA) (step 1); melt-co-extruding the first resin and the second resin to obtain a two-layer laminated sheet (step 2); and biaxially stretching and heat-setting the laminated sheet to obtain a laminate (step 3), the laminate comprising a first layer including the first polylactic acid (PLA) and a polyhydroxyalkanoate (PHA), and a second layer disposed on one surface of the first layer and including the second polylactic acid (PLA), the first layer including more than 0% by weight and less than 30% by weight of the polyhydroxyalkanoate (PHA) based on the total weight of the first layer.
[0017] Furthermore, the present invention provides an environmentally friendly packaging material comprising the biaxially stretched film or laminate. Effect of the Invention
[0018] The biaxially stretched film according to the present invention contains polylactic acid (PLA) and polyhydroxyalkanoate (PHA), and contains PHA in a specific content range. The film's composite flexible noise index (LSN) satisfies a specific range, thereby enabling the film to simultaneously have excellent strength and flexibility, low noise level, and improved optical and thermal properties.
[0019] In addition, the laminate according to the present invention includes a first layer and a second layer having a specific composition, and thus has excellent strength and flexibility at the same time, a low noise level, and improved optical properties and thermal properties. In addition, since the first layer and the second layer have good interlayer compatibility, excellent interlayer adhesion properties can be maintained.
[0020] Furthermore, the method for producing a laminate according to the present invention can further improve processability and productivity by an economical and efficient method.
[0021] Furthermore, the biaxially oriented film and the laminate are biodegradable and completely decompose when buried in a landfill, and therefore have environmentally friendly properties. Therefore, they can be used as packaging materials in a variety of fields, and therefore high-quality packaging materials can be provided. [Brief description of the drawings]
[0022] [Figure 1] FIG. 1 is a schematic diagram of a stack according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram of a stack according to another embodiment of the present invention. [Diagram 3] FIG. 3 is a schematic diagram of a stack according to yet another embodiment of the present invention. [Figure 4] FIG. 4 shows a schematic diagram of a method for producing a laminate according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] The present invention will be described in detail below with reference to the following examples. The implementation examples are not limited to the contents disclosed below, and may be modified in various forms without departing from the spirit of the invention.
[0024] In this specification, when a part is said to "comprise" a certain component, this means that it may further include other components, rather than excluding other components, unless specifically stated to the contrary.
[0025] In this specification, the singular expressions "a," "an," and "the" are to be construed as including the singular or plural as the context requires, unless otherwise specified.
[0026] In addition, all numerical ranges indicating the physical properties, dimensions, reaction conditions, and the like of the components described in this specification should be understood to be modified in all cases by the term "about" unless otherwise specified.
[0027] Meanwhile, in this specification, the terms "first layer", "second layer", "first" and "second" are used to describe various components, and the components are not limited by the terms. The terms are used only to distinguish one component from another.
[0028] In addition, the criteria for "one side" / "hitting surface" or "top" / "bottom" of each component will be explained based on the drawings, and these terms are only used to distinguish the components and may be interchangeable in actual application.
[0029] In this specification, when a component is described as being formed above or below another component, this includes all cases in which the component is directly formed above or below the other component, or indirectly formed via still other components.
[0030] In addition, the size of each component in the drawings may be exaggerated for illustrative purposes and does not represent the actual size. In addition, the same reference numerals refer to the same components throughout the specification.
[0031] [Biaxially oriented film] In one embodiment, a biaxially stretched film is provided that contains polylactic acid (PLA) and polyhydroxyalkanoate (PHA), and that contains more than 0% by weight and less than 30% by weight of polyhydroxyalkanoate (PHA) based on the total weight of the biaxially stretched film, and when the thickness of the film is 19 μm to 21 μm, the flexible noise composite index (LSN) represented by the following formula 1-1 is 20 or less.
[0032] <Formula 1-1> Flexible noise composite index (LSN) = N AVG ×LS In the above formula 1-1, N AVG is the average sound level (dB) calculated by measuring the maximum sound level five times when a class 2 sound level meter specified in KS C IEC61672-1 is aimed toward the noise source and a biaxially stretched film test piece with a width of 21 cm and a length of 29.5 cm is swung at a speed of 120 times per minute at a point 1.2m to 1.5m above the ground. The unit is omitted. The LS is a unit-free value that indicates the loop stiffness (gf) measured by fixing a loop-shaped biaxially stretched film specimen having a width of 1.5 cm and a length of 18 cm to a loop stiffness tester and measuring the load at the center of the loop based on ASTM D747.
[0033] In one embodiment, the inclusion of polylactic acid (PLA) and polyhydroxyalkanoate (PHA) can improve flexibility and reduce noise level, and in particular, the inclusion of polyhydroxyalkanoate (PHA) in an amount of more than 0% by weight and less than 30% by weight based on the total weight of the biaxially stretched film can improve flexibility while maintaining appropriate strength, further improve optical properties, and provide a film with low thermal shrinkage at high temperatures of 100° C. or higher and small thickness deviation. Furthermore, by controlling the composite flexibility noise index (LSN) represented by the above formula 1-1 to 20 or less, strength, flexibility, and noise level can be further improved, and by providing the film as a biaxially stretched film stretched in both directions, the physical properties and formability of the film can be further improved, thereby realizing a high-quality packaging material, which is technically significant.
[0034] The biaxially stretched film according to the embodiment will be described in more detail below. A biaxially oriented film according to one implementation includes polylactic acid (PLA) and polyhydroxyalkanoate (PHA).
[0035] Unlike petroleum-based resins, polylactic acid (PLA) is based on biomass, making it possible to utilize renewable resources. It also emits less carbon dioxide, the main cause of global warming, during production compared to existing resins, and is biodegradable by moisture and microorganisms when buried, making it environmentally friendly.
[0036] The polylactic acid (PLA) may have a weight average molecular weight (Mw) of 100,000 to 1,000,000 g / mol, for example, 100,000 to 800,000 g / mol, 100,000 to 500,000 g / mol, or 100,000 to 300,000 g / mol. The weight average molecular weight (Mw) may be measured by gel permeation chromatography (GPC). If the weight average molecular weight (Mw) of the polylactic acid (PLA) is outside the above range, the mechanical strength and heat resistance of the film may be reduced compared to when it is within the above range.
[0037] The polylactic acid (PLA) may include L-lactic acid, D-lactic acid, DL-lactic acid, or a combination thereof. Specifically, the polylactic acid (PLA) may be a random copolymer of L-lactic acid and D-lactic acid. In this case, the content of the L-lactic acid may be 80% by weight to 99% by weight, 83% by weight to 99% by weight, or 85% by weight to 99% by weight based on the total weight of the polylactic acid.
[0038] The polylactic acid (PLA) may have a melting temperature (Tm) of 100°C to 250°C, 110°C to 220°C, or 120°C to 200°C.
[0039] The polylactic acid (PLA) may have a glass transition temperature (Tg) of 30°C to 80°C, 40°C to 80°C, 40°C to 70°C, or 45°C to 65°C.
[0040] The polylactic acid (PLA) may comprise more than 70% by weight, 75% by weight or more, 80% by weight or more, 85% by weight or more, 88% by weight or more, 90% by weight or more, 93% by weight or more, or 95% by weight or more, based on the total weight of the biaxially stretched film. The polylactic acid (PLA) may comprise less than 100% by weight, 99% by weight or less, 98% by weight or less, 97% by weight or less, or 95% by weight or less, based on the total weight of the biaxially stretched film.
[0041] Specifically, the polylactic acid (PLA) may be contained in an amount of more than 70% by weight and less than 100% by weight, more than 70% by weight and less than 99% by weight, 75% by weight to 99% by weight, 75% by weight to 98% by weight, 75% by weight to 97% by weight, 80% by weight to 97% by weight, 85% by weight to 97% by weight, 90% by weight to 97% by weight, 95% by weight to less than 100% by weight, 95% by weight to 97% by weight, or 90% by weight to 95% by weight.
[0042] If the content of polylactic acid (PLA) is too low, the tensile strength may decrease, the heat shrinkage rate may increase, and the optical properties such as transparency and light transmittance may decrease, whereas if the content of polylactic acid (PLA) is too high, the brittleness may increase, the flexibility may decrease, and the product may be easily broken or cracked, and may be noisy.
[0043] In particular, polylactic acid (PLA) has a high brittleness and the film tends to harden when the operating temperature range is below 20°C, so it is prone to cracking or breaking when it receives an impact in winter. When the operating temperature range is above 35°C, the film tends to lose elasticity and become soft, and is noisy, so its use is limited.
[0044] Therefore, in the embodiment, polyhydroxyalkanoate (PHA), which has excellent flexibility and low noise level, is mixed and used together with the polylactic acid (PLA).
[0045] In particular, in the biaxially stretched film of the embodiment, the content of polyhydroxyalkanoate (PHA) contained in the biaxially stretched film is important in order to achieve excellent strength, flexibility, improved optical properties, thermal properties, and improved noise level.
[0046] A biaxially stretched film according to an embodiment can include greater than 0% and less than 30% by weight of polyhydroxyalkanoate (PHA), based on the total weight of the biaxially stretched film.
[0047] Specifically, the biaxially stretched film may contain polyhydroxyalkanoate (PHA) in an amount of more than 0 wt% to less than 30 wt%, 1 wt% to less than 30 wt%, 1 wt% to 25 wt%, 2 wt% to 25 wt%, 3 wt% to 25 wt%, 3 wt% to 20 wt%, 3 wt% to 15 wt%, 3 wt% to 10 wt%, more than 0 to 5 wt%, 3 wt% to 5 wt%, or 5 wt% to 10 wt%, based on the total weight of the biaxially stretched film.
[0048] If the content of the polyhydroxyalkanoate (PHA) is too high, the tensile strength may decrease, the heat shrinkage rate may increase, the extrusion processability may decrease, and the optical properties may decrease, whereas if the content of the polyhydroxyalkanoate (PHA) is too low, the brittleness may increase, the flexibility may decrease, the material may be easily broken or cracked, and the noise level may increase.
[0049] According to an embodiment, the mixing weight ratio of the polylactic acid (PLA) and the polyhydroxyalkanoate (PHA) may be more than 70 to less than 100: more than 0 to less than 30, for example, 80 to 97: 3 to 20, for example, 80 to 95: 5 to 20, for example, 90 to 97: 3 to 10, for example, 90 to 95: 5 to 10, or for example, 95 to 97: 3 to 5. When the mixing weight ratio of the polylactic acid (PLA) and the polyhydroxyalkanoate (PHA) satisfies the above range, it is possible to improve flexibility while maintaining appropriate strength, improve optical properties and thermal properties, and reduce noise level.
[0050] According to a realization example, the polyhydroxyalkanoate (PHA) can be a copolymerized polyhydroxyalkanoate (PHA).
[0051] Specifically, the copolymerized polyhydroxyalkanoate (PHA) may be a polyhydroxyalkanoate (PHA) with a controlled degree of crystallinity (crystallinity).
[0052] For example, the polyhydroxyalkanoate (PHA) may be a copolymerized polyhydroxyalkanoate (PHA) having controlled crystallinity, including a copolymerized polyhydroxyalkanoate containing at least one unit of the following formula 1 and at least one unit of the following formula 2: [Chemical formula 1] JPEG2025032119000002.jpg2252In the above Chemical Formula 1, R1 is a substituted C1-C8 alkylene; m is an integer of 1 or greater.
[0053] [Chemical formula 2] JPEG2025032119000003.jpg2251In the above Chemical Formula 2, R2 is a substituted or unsubstituted C1 to C8 alkylene; n is an integer of 1 or greater.
[0054] In this regard, in the above Chemical Formulas 1 and 2, unless otherwise specified, "substituted" may include substituted or unsubstituted alkyl groups, specifically substituted or unsubstituted C1 to C8 alkyl groups.
[0055] The polyhydroxyalkanoate (PHA) may be a polyester containing only the units of the chemical formula 1 and the units of the chemical formula 2 as polymerized units, or may contain the units of the chemical formula 1 and the units of the chemical formula 2 as polymerized units, and may further contain different polymerized units other than the above. Also, the units of the chemical formula 2 may be repeated randomly.
[0056] According to an embodiment, in the formula 1, R1 can be, for example, a substituted C2-C8 alkylene, a substituted C3-C8 alkylene, or a substituted C3-C6 alkylene, and m can be 1-12000.
[0057] In the above Chemical Formula 2, R2 may be, for example, a substituted or unsubstituted C2-C8 alkylene, a substituted or unsubstituted C3-C8 alkylene, or a substituted or unsubstituted C4-C8 alkylene. For example, in the above Chemical Formula 2, R2 may include an unsubstituted alkylene. In addition, n may be 1 to 12,000.
[0058] Additionally, in the above Chemical Formulas 1 and 2, the above substituents may each include C1 to C8 alkyl, C1 to C6 alkyl, or C1 to C4 alkyl.
[0059] Specifically, the polyhydroxyalkanoate (PHA) may contain at least one unit of the following formula 1-1 and at least one unit of the following formula 2-1.
[0060] [Chemical formula 1-1] JPEG2025032119000004.jpg3150In the above Chemical Formula 1-1, R3 is methyl, ethyl, or propyl; m is an integer of 1 or greater.
[0061] [Chemical formula 2-1] JPEG2025032119000005.jpg2956In the above Chemical Formula 2-1, n is an integer of 1 or greater.
[0062] Specifically, in the above Chemical Formula 1-1, R3 may be methyl and m may be 1 to 12,000.
[0063] In the above Chemical Formula 2-1, n can be 1 to 12,000.
[0064] The crystallinity-controlled polyhydroxyalkanoate (PHA) may be one in which the crystallinity and amorphousness are controlled by increasing the irregularity in the molecular structure, and specifically, the type of monomer, the ratio of monomers, or the type and / or content of isomers may be adjusted.
[0065] According to an embodiment, the polyhydroxyalkanoate (PHA) is a copolymerized polyhydroxyalkanoate (PHA) including a unit of the chemical formula 1 and a unit of the chemical formula 2, and the content of the unit of the chemical formula 2 may be 1 wt % or more, 3 wt % or more, 5 wt % or more, 10 wt % or more, and 60 wt % or less, 55 wt % or less, or 50 wt % or less, based on the total weight of the copolymerized polyhydroxyalkanoate.
[0066] For example, the polyhydroxyalkanoate (PHA) may be a copolymerized polyhydroxyalkanoate (PHA) containing units of the chemical formula 1 and units of the chemical formula 2, and the content of the units of the chemical formula 2 may be 1 to 60% by weight, 5 to 50% by weight, 10 to 60% by weight, 10 to 50% by weight, 15 to 60% by weight, 15 to 50% by weight, 20 to 60% by weight, 20 to 50% by weight, 25 to 60% by weight, 25 to 50% by weight, 30 to 60% by weight, 30 to 50% by weight, 35 to 60% by weight, 35 to 50% by weight, 40 to 60% by weight, 40 to 50% by weight, 45 to 60% by weight, 45 to 50% by weight, or 46 to 50% by weight.
[0067] According to the implementation, the polyhydroxyalkanoate (PHA) may include isomers. For example, the polyhydroxyalkanoate (PHA) may include structural isomers, enantiomers, or geometric isomers. Specifically, the polyhydroxyalkanoate (PHA) may include structural isomers.
[0068] According to a realization example, the copolymerized polyhydroxyalkanoate (PHA) can be an amorphous polyhydroxyalkanoate (PHA).
[0069] When the copolymerized polyhydroxyalkanoate (PHA) is an amorphous polyhydroxyalkanoate (PHA), there is compatibility between the resins, which may result in improved optical properties, compared to when a crystalline polyhydroxyalkanoate (PHA) is used as the polyhydroxyalkanoate (PHA) and mixed with the polylactic acid (PLA) to produce a film.
[0070] When the copolymerized polyhydroxyalkanoate (PHA) is an amorphous polyhydroxyalkanoate (PHA), the amorphous polyhydroxyalkanoate (PHA) is a copolymerized polyhydroxyalkanoate (PHA) containing units of the chemical formula 1 and units of the chemical formula 2, and may contain 15% by weight to 60% by weight of units of the chemical formula 2 based on the total weight of the copolymerized polyhydroxyalkanoate (PHA).
[0071] In the polyhydroxyalkanoate (PHA), the amorphousness can increase as the content of the unit of Chemical Formula 2 increases, so in the biaxially stretched film according to the embodiment, the content of the unit of Chemical Formula 2 in the amorphous polyhydroxyalkanoate (PHA) can be important.
[0072] For example, the amorphous polyhydroxyalkanoate (PHA) may contain the unit of Chemical Formula 2 in an amount of 15 to 60% by weight, 15 to 50% by weight, 20 to 60% by weight, 20 to 50% by weight, 25 to 60% by weight, 25 to 50% by weight, 30 to 60% by weight, 30 to 50% by weight, 35 to 60% by weight, 35 to 50% by weight, 40 to 60% by weight, 40 to 50% by weight, 45 to 60% by weight, 45 to 50% by weight, or 46 to 50% by weight, based on the total weight of the polyhydroxyalkanoate (PHA).
[0073] The biaxially stretched film according to the embodiment contains the unit of Chemical Formula 2 in the above range, and therefore when polyhydroxyalkanoate (PHA) is mixed with polylactic acid (PLA), there is compatibility between the resins and excellent optical properties, which is advantageous in that the optical properties of the film can be further improved. If the unit of Chemical Formula 2 in polyhydroxyalkanoate (PHA) is less than 15% by weight, the compatibility between the resins may be poor, and the transparency and light transmittance may be reduced.
[0074] According to an embodiment, the amorphous polyhydroxyalkanoate (PHA) is a copolymerized polyhydroxyalkanoate (PHA) containing 3-hydroxybutyrate (3-HB) units and 4-hydroxybutyrate (4-HB) units, and the 4-hydroxybutyrate (4-HB) units may be contained in an amount of 15% by weight to 60% by weight based on the total weight of the copolymerized polyhydroxyalkanoate (PHA).
[0075] In the polyhydroxyalkanoate (PHA), the amorphousness increases as the content of the 4-hydroxybutyrate (4-HB) unit increases, so in the biaxially stretched film according to the embodiment, the content of the 4-hydroxybutyrate (4-HB) unit in the amorphous polyhydroxyalkanoate (PHA) may be important.
[0076] For example, the 4-hydroxybutyrate (4-HB) units may be contained in an amount of, for example, 20 to 60% by weight, for example, 25 to 60% by weight, for example, 25 to 50% by weight, for example, 30 to 60% by weight, for example, 30 to 50% by weight, for example, 35 to 60% by weight, for example, 35 to 50% by weight, for example, 40 to 60% by weight, for example, 40 to 50% by weight, for example, 45 to 60% by weight, for example, 45 to 50% by weight, for example, 46 to 60% by weight, or for example, 46 to 50% by weight, based on the total weight of the copolymerized polyhydroxyalkanoate (PHA).
[0077] The biaxially stretched film according to the embodiment contains 4-hydroxybutyrate (4-HB) units in the above range, and thus has the advantage that when polyhydroxyalkanoate (PHA) is mixed with polylactic acid (PLA), the resins are compatible with each other, which can improve the optical properties of the film. If the 4-hydroxybutyrate (4-HB) units are less than 15% by weight, the compatibility between the resins is poor, and the optical properties may be degraded.
[0078] The polyhydroxyalkanoate (PHA) may be a polyester containing only 3-hydroxybutyrate (3-HB) units and 4-hydroxybutyrate (4-HB) units as polymerized units (i.e., the polymerized units consist of only 3-hydroxybutyrate (3-HB) units and 4-hydroxybutyrate (4-HB) units), or may contain 3-hydroxybutyrate (3-HB) units and 4-hydroxybutyrate (4-HB) units as polymerized units, and may further contain different polymerized units other than those mentioned above. In addition, the 4-hydroxybutyrate (4-HB) units may be repeated randomly.
[0079] The different polymerized units include lactate (LA), glycolate (GA), 3-hydroxypropionate (3HP), 3-hydroxyvalerate (3HV), 5-hydroxyvalerate (5HV), 5-hydroxyhexanoate (5HH), 6-hydroxyhexanoate (6HH), 3-hydroxyhexanoate (3HH), or hydroxyalkanoates having 7 or more carbon atoms.
[0080] The polyhydroxyalkanoate (PHA) may have a weight average molecular weight (Mw) of 100,000 g / mol to 1,000,000 g / mol, 100,000 g / mol to 900,000 g / mol, 120,000 g / mol to 850,000 g / mol, or 150,000 g / mol to 800,000 g / mol. The weight average molecular weight (Mw) may be measured by gel permeation chromatography (GPC).
[0081] The polyhydroxyalkanoate (PHA) may have a glass transition temperature (Tg) of −5° C. to −50° C., −15° C. to −40° C., or −20° C. to −40° C. When the weight average molecular weight (Mw) and glass transition temperature (Tg) of the amorphous polyhydroxyalkanoate (PHA) satisfy the above ranges, optical properties such as transparency and light transmittance are improved, which may be more advantageous in achieving the intended noise improvement effect and flexibility improvement effect.
[0082] According to one implementation, the biaxially stretched film may further comprise a filler. The filler may include an organic filler, an inorganic filler, or a mixture thereof.
[0083] The organic filler may include an organic filler comprising a material selected from hard acrylate, polystyrene, nylon, and soft acrylate.
[0084] The inorganic filler may be one or more selected from the group consisting of barium sulfate, silica, and calcium carbonate.
[0085] The filler may be an inorganic filler and may include, for example, silica.
[0086] By including the filler, the biaxially stretched film can have excellent slip properties and improved processability, and can provide excellent quality.
[0087] The particle size of the filler may be 0.1 μm to 6.0 μm. For example, the particle size of the filler may be 1.0 μm to 5.5 μm or 2.0 μm to 5.2 μm.
[0088] The biaxially stretched film may contain the filler in an amount of 0.01 to 3 wt % based on the total weight of the biaxially stretched film. For example, the biaxially stretched film may contain the filler in an amount of 0.05 to 2.5 wt %, 0.1 to 2 wt %, 0.2 to 1.7 wt %, or 0.5 to 1.5 wt % based on the total weight of the biaxially stretched film.
[0089] According to one embodiment, the biaxially stretched film may have a composite soft noise index (LSN) of 20 or less, as expressed by the formula 1-1, when the thickness of the film is 19 μm to 21 μm.
[0090] The composite flexible noise index (LSN) represented by the formula 1-1 is expressed as the product of the average noise intensity and the loop stiffness of the biaxially stretched film, which is an index showing the degree of the composite properties of the flexibility and noise intensity of the biaxially stretched film. Therefore, the composite flexible noise index (LSN) can be a measure of the quality of a packaging material containing the biaxially stretched film.
[0091] The soft noise composite index (LSN) is the average noise intensity (N AVG ) is lower, and the average noise level (N AVG The soft noise composite index (LSN) may be higher when the loop stiffness (LS) is higher. Also, the soft noise composite index (LSN) may be lower when the loop stiffness (LS) is lower, and higher when the loop stiffness (LS) is higher.
[0092] When the composite flexible noise index (LSN) having such characteristics satisfies the above-mentioned specific range or less, the biaxially stretched film has excellent mechanical properties, optical properties and thermal properties, and can reduce noise intensity.
[0093] Specifically, the biaxially stretched film may have a composite flexible noise (LSN) of, for example, 20 or less, 19 or less, 18 or less, 17 or less, 16 or less, or 15 or less. If the composite flexible noise (LSN) of the biaxially stretched film exceeds 20, the film may have reduced flexibility and increased brittleness, and may have increased noise, which may result in reduced quality when used as a packaging material.
[0094] The composite flexible noise index (LSN) of the biaxially stretched film may be the same or different depending on the longitudinal direction (MD) and transverse direction (TD) of the biaxially stretched film, where the longitudinal direction (MD) of the biaxially stretched film refers to the length direction or machine direction, and the transverse direction (TD) of the biaxially stretched film refers to the width direction perpendicular to the longitudinal direction (MD).
[0095] Specifically, the biaxially stretched film was subjected to a flexible noise composite index (LSN MD ) can be, for example, 5 to 20, 5 to 19, 5 to 18, 10 to 18, 14 to 18, or 15 to 18.
[0096] The transverse direction (TD) flexibility noise composite index (LSN TD ) can be, for example, 5 to 20, 5 to 19, 8 to 19, 10 to 19, 12 to 19, or 13 to 19.
[0097] The biaxially stretched film is LSN MD Only LSN may be satisfied TD Only LSN may be satisfied MD and LSN TD In this case, the biaxially stretched film according to the embodiment can improve flexibility while maintaining an appropriate tensile strength, and can reduce noise, which is more advantageous in achieving the intended effect and can provide an environmentally friendly packaging material with excellent quality.
[0098] On the other hand, in the formula 1-1, the average noise intensity (N AVG ) was measured by using a sound level meter of class 2 or higher as specified in KS C IEC61672-1, pointing it toward the noise source, shaking one piece of the biaxially stretched film at a constant speed for 1 minute at a point 1.2m to 1.5m above the ground, measuring the noise intensity and recording the maximum noise intensity, and repeating this five times to obtain the average value of the maximum noise intensity for each time, which was defined as the average noise intensity. The noise intensity can be measured at a height of 1.2m to 1.5m above the ground, and if there is an obstacle with a height of more than 1.5m at the measurement point, it can be measured at a point about 1.0m to 3.5m away from the obstacle in the direction of the noise source.
[0099] The biaxially stretched film has an average noise intensity (N AVG ) is preferable in terms of providing a high-quality packaging material.
[0100] Specifically, the average noise intensity (N AVG ) may be, for example, 86 dB or less, for example 85 dB or less, for example 84 dB or less, for example 83 dB or less, or for example 82.5 dB or less.
[0101] The average noise intensity (N AVG ) is 86 dB or less, it is advantageous in controlling the composite soft noise index (LSN) of the above formula 1-1 to 20 or less, and it is possible to provide a packaging material of good quality by improving noise.
[0102] In addition, in the formula 1-1, the loop stiffness (LS) of the biaxially stretched film is measured based on ASTM D747 by fixing a loop-shaped biaxially stretched film test piece having a width of 1.5 cm and a length of 18 cm to a loop measuring device (Loop Stiffness Tester, Toyo Seiki Seisakusho) and measuring the load at the center of the loop, and is an index showing the degree of flexibility of the biaxially stretched film.
[0103] The loop stiffness (LS) of the biaxially stretched film may be 0.23 gf or less, 0.22 gf or less, 0.21 gf or less, or 0.20 gf or less. Specifically, the loop stiffness (LS) of the biaxially stretched film may be, for example, 0.10 to 0.23 gf, for example, 0.10 to 0.22 gf, for example, 0.10 to 0.21 gf, or for example, 0.10 to 0.20 gf.
[0104] The lower the loop stiffness (LS) of the biaxially stretched film, the greater the flexibility, and the higher the loop stiffness (LS) of the biaxially stretched film, the less flexibility there may be.
[0105] Additionally, the loop stiffness (LS) of the biaxially stretched film may be the same or different in the machine direction (MD) and the transverse direction (TD) of the biaxially stretched film.
[0106] Specifically, the biaxially stretched film has a longitudinal (MD) loop stiffness (LS MD) may be, for example, 0.10 to 0.23 gf, for example, 0.10 to 0.22 gf, for example, 0.12 to 0.22 gf, for example, 0.12 to 0.21 gf, for example, 0.15 to 0.21 gf.
[0107] The loop stiffness (LS) in the transverse direction (TD) of the biaxially stretched film TD ) may be, for example, 0.10 to 0.23 gf, for example, 0.10 to 0.22 gf, for example, 0.12 to 0.22 gf, or for example, 0.14 to 0.22 gf.
[0108] The biaxially stretched film is a LS MD Only satisfied with LS TD Only LS may be satisfied MD and L.S. TD In this case, the biaxially stretched film according to the embodiment is more effective in controlling the composite soft noise index (LSN) represented by the formula 1-1 within the above range, and is therefore more advantageous in achieving the desired effect, and can provide an environmentally friendly packaging material with excellent quality.
[0109] On the other hand, the biaxially stretched film has a thermal shrinkage rate (S 100 ) may be 15% or less.
[0110] <Formula 1-2> Heat shrinkage rate (S 100 )={(L 25 -L 100 ) / L 25}×100 In the above formula 1-2, L 25 is the initial length (mm) of the biaxially stretched film specimen at 25°C, L 100 is the length (mm) of a biaxially stretched film test piece measured immediately after being held in a hot air blower at 100°C for 5 minutes.
[0111] The thermal shrinkage rate (S 100) is a value obtained by converting the degree of thermal shrinkage of a biaxially stretched film test piece into a percentage at a hot air temperature of 100°C, and is a value calculated as a percentage of the initial length of the biaxially stretched film test piece and the length change amount of the biaxially stretched film test piece measured immediately after being retained in a hot air blower for 5 minutes.
[0112] The heat shrinkage rate (S 100 ) can be calculated by cutting a biaxially stretched film into a test piece of 150 mm length and 2 cm width regardless of the direction, and then measuring the initial length at room temperature and the length of the biaxially stretched film test piece after it has been left in a hot air oven at 100°C for 5 minutes.
[0113] The heat shrinkage rate (S 100 ) may be 15% or less, 12% or less, 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, or 4.5% or less.
[0114] The heat shrinkage rate (S 100 ) satisfies the above range or less, the degree of thermal shrinkage at high hot air temperatures of 100° C. or more is small, so that the thermal properties are improved and the printability and moldability can be further improved.
[0115] The heat shrinkage rate (S 100 ) may be the same or different in the machine direction (MD) and transverse direction (TD) of the biaxially oriented film.
[0116] Specifically, the thermal shrinkage rate (S MD100 ) can be 15% or less, 12% or less, 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, 4.5% or less, or 4% or less.
[0117] The thermal shrinkage rate (S TD100 ) can be, for example, 15% or less, 12% or less, 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, or 4.5% or less.
[0118] If the thermal shrinkage ratios of the biaxially stretched film in the machine direction (MD) and the transverse direction (TD) exceed the above ranges, problems will arise in printing due to severe shrinkage in the machine direction and the transverse direction caused by hot air during printing and lamination, and curling will occur severely after printing, resulting in a phenomenon in which the film is rolled up, which is not preferable.
[0119] Meanwhile, the biaxially stretched film according to the embodiment may have a forming index (FI) represented by the following formula 1-3 of 65 or more.
[0120] <Formula 1-3> Forming index (FI)=TS / LS In the above formula 1-3, TS is a measurement of the tensile strength (kgf / mm) of a specimen cut to a length of approximately 100 mm and a width of 15 mm based on ASTM D882. The specimen is attached so that the chuck distance is 50 mm, and the tensile strength (kgf / mm) of the specimen is measured at room temperature using a universal testing machine (UTM). 2 ) without units, and LS is as defined above.
[0121] The forming index (FI) of the biaxially stretched film is the ratio of the tensile strength to the loop stiffness of the biaxially stretched film, and can indicate a measure of whether the tensile strength and flexibility are adequate.
[0122] That is, according to the embodiment, the biaxially stretched film has a main feature that it has an increased flexibility and soft properties while maintaining an appropriate range of strength, for example, tensile strength. In this case, the biaxially stretched film has excellent formability and is advantageous for various application expansion.
[0123] The forming index (FI) of the biaxially stretched film may be, for example, 65 or more, 68 or more, 70 or more, 75 or more, 80 or more, 85 or more, 90 or more, 95 or more, or 100 or more. Specifically, the forming index (FI) of the biaxially stretched film may be, for example, 65 to 120, for example, 65 to 110, or for example, 65 to 105. If the forming index (FI) of the biaxially stretched film is less than 65, the flexibility may decrease and the film may be easily broken, or the strength may decrease and various problems may occur during processing or molding, and the application to various uses may be limited, and the quality of the molded product, such as a packaging material, to which the biaxially stretched film is applied may decrease or the film may be defective.
[0124] The forming index (FI) of the biaxially stretched film may be the same or different in the machine direction (MD) and the transverse direction (TD) of the biaxially stretched film.
[0125] Specifically, the forming index (FI) of the biaxially stretched film in the machine direction (MD) MD ) may be, for example, 65 to 90, for example, 70 to 90, or for example, 70 to 80.
[0126] The forming index (FI) of the biaxially stretched film in the transverse direction (TD) TD ) may be, for example, 80 to 110, for example, 85 to 110, or for example, 90 to 110.
[0127] The biaxially stretched film is FI MD Only satisfied or FI TD May only satisfy FI MD and F.I. TD In this case, the biaxially stretched film according to the embodiment can improve flexibility while maintaining an appropriate tensile strength, and can provide an environmentally friendly packaging material with excellent quality.
[0128] In addition, in the formula 1-3, the loop stiffness (LS) of the biaxially stretched film is as defined above.
[0129] In addition, the tensile strength of the biaxially stretched film may be measured by preparing a biaxially stretched film test piece according to ASTM D882, cutting it to a length of 100 mm and a width of 15 mm, and mounting it so that the chuck distance is 50 mm. The tensile strength may be measured by using an INSTRON universal testing machine (UTM, model name 5966) at a tensile speed of 200 mm / min at room temperature of 25° C., and then using a program built into the machine.
[0130] The tensile strength is, for example, 9 to 25 kgf / mm 2 , for example 9.5~22kgf / mm 2 , for example 10~22kgf / mm 2 , for example 12~20kgf / mm 2 , or for example 13 to 20 kgf / mm 2 It could be.
[0131] When the tensile strength satisfies the above range, the productivity, processability and formability of the biaxially stretched film can be improved at the same time.
[0132] In addition, the tensile strength (TS) of the biaxially stretched film may be the same or different depending on the machine direction (MD) and the transverse direction (TD) of the biaxially stretched film.
[0133] Specifically, the tensile strength (TS) of the biaxially stretched film in the machine direction (MD) MD ) is, for example, 9 to 25 kgf / mm 2 , for example 9.5~22kgf / mm 2 , for example 10~22kgf / mm 2 , for example 12~20kgf / mm 2 , or for example 13 to 18 kgf / mm 2 It could be.
[0134] The tensile strength (TS) of the biaxially stretched film in the transverse direction (TD) TD ) is, for example, 9 to 25 kgf / mm 2 , 10~25kgf / mm 2 , for example 11 to 23 kgf / mm 2 , for example 12~23kgf / mm 2, or for example 15-20kgmm 2 It could be.
[0135] The biaxially stretched film is MD Only satisfied with the TS TD Only TS may be satisfied MD and T.S. TD In this case, the biaxially stretched film according to the embodiment can control the formability index (FI) represented by the above formula 1-3 within the above range, and can simultaneously improve the productivity, processability, and formability, thereby providing an environmentally friendly packaging material with excellent quality.
[0136] On the other hand, the biaxially stretched film has a strain-stress curve of 200 kgf / mm 2 ~380kgf / mm 2 , 200kgf / mm 2 ~360kgf / mm 2 , 200kgf / mm 2 ~350kgf / mm 2 , 250kgf / mm 2 ~350kgf / mm 2 , or 260 kgf / mm 2 ~350kgf / mm 2 The modulus is 200 kgf / mm 2 If the modulus is less than 380 kgf / mm, the resistance to mechanical tension during processing such as printing or lamination is insufficient, and wrinkles may occur in the running direction, causing problems in printing, or the film may break during running, which is undesirable. 2 If the modulus exceeds 100%, the stiffness of the film increases and the film may be easily broken or cracked by an external impact. Also, within the above range, the lower the modulus, the better the flexibility.
[0137] Meanwhile, the biaxially stretched film may have a thickness deviation of 10 μm or less across the entire width of the film. Specifically, the biaxially stretched film may have a thickness deviation of 9 μm or less, 8.5 μm or less, 8 μm or less, 7 μm or less, 6.5 μm or less, or 5 μm or less across the entire width of the film.
[0138] When the biaxially stretched film according to the embodiment contains amorphous polyhydroxyalkanoate (PHA), it has excellent stretching uniformity, and therefore it is possible to provide a biaxially stretched film with little thickness deviation.
[0139] On the other hand, the biaxially stretched film can have excellent optical properties. Specifically, the biaxially stretched film may have a haze of 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, or 5% or less. If the haze exceeds the above range, the transparency of the film may be significantly reduced, which may limit its use in packaging applications where the contents of the contents can be seen.
[0140] When the biaxially stretched film according to the realization contains a certain content of amorphous polyhydroxyalkanoate (PHA), the biaxially stretched film can provide a transparent biaxially stretched film due to low haze.
[0141] The biaxially stretched film may also have a light transmittance of 90% or more, 92% or more, or 93% or more.
[0142] Furthermore, the biaxially stretched film is characterized by having a biodegradability of 90% or more as measured by the amount of carbon dioxide generated based on KS M3100-1. Biodegradability is the ratio of decomposition to a standard substance (e.g., cellulose) in the same period, and the Ministry of Environment of the Republic of Korea defines a substance as biodegradable when its biodegradability is 90% or more compared to the standard substance.
[0143] The above-mentioned structural and physical property characteristics of the biaxially stretched film according to the embodiment can be efficiently achieved by manufacturing the biaxially stretched film according to the embodiment. The method for producing the biaxially stretched film will now be described in detail.
[0144] [Manufacturing method of biaxially stretched film] A method for producing a biaxially stretched film may include a first step of mixing polylactic acid (PLA) and polyhydroxyalkanoate (PHA) and then melt-extruding the mixture to produce a sheet, a second step of biaxially stretching the melt-extruded sheet to produce a film, and a third step of heat-setting the biaxially stretched film.
[0145] Specifically, the first step may include mixing polylactic acid (PLA) and polyhydroxyalkanoate (PHA) and then melt-extruding the mixture to produce a sheet.
[0146] The contents or mixing weight ratios of the polylactic acid (PLA) and polyhydroxyalkanoate (PHA) are as described above.
[0147] During the mixing, a filler may be added to improve lubricity and quality. The type, content, particle size, etc. of the filler are as described above.
[0148] The melt extrusion is carried out at 180° C. to 250° C., and after the melt extrusion, the sheet can be obtained by contacting the sheet with a cooling roll cooled to about 10° C. to 30° C.
[0149] The second step may include biaxially stretching the melt extruded sheet to produce a film.
[0150] The melt-extruded sheet may be preheated to 50°C to 80°C, and then stretched at 40°C to 100°C in the machine direction (MD) by 2 to 4 times its original size.
[0151] For example, the melt-extruded sheet may be preheated to 50°C to 80°C, and then passed through rolls in a stretching section at 70°C to 100°C to be longitudinally stretched 2 to 4 times.
[0152] The stretched film can be stretched transversely at 50°C to 110°C by 3 to 5 times its original size in the transverse direction (MD).
[0153] For example, the stretched film can be stretched transversely 3 to 5 times in a tenter section divided into a first section where the average temperature in the initial 30% section is 80°C to 105°C, and a second section where the average temperature in the latter 70% section is 80°C to 110°C.
[0154] In some embodiments, the film can be provided as a biaxial film that is stretched in both directions, thereby improving the film's physical properties and formability, resulting in high-quality packaging materials.
[0155] If a uniaxial film is stretched in one of the machine and transverse directions, the thickness deviation of the film will be so great that the strength of the other direction, which is not stretched, will decrease significantly, and the thermal properties may also decrease.
[0156] The third step may include heat setting the biaxially stretched film.
[0157] The heat setting step may be carried out at 50°C to 150°C, 70°C to 150°C, 100°C to 150°C, or 120°C to 150°C.
[0158] Producing the biaxially stretched film by the manufacturing method of the embodiment may be more effective in producing a biaxially stretched film having a desired structure and physical properties.
[0159] [Laminate] In one embodiment, a laminate is provided that includes a first layer including a first polylactic acid (PLA) and a polyhydroxyalkanoate (PHA), and a second layer disposed on one side of the first layer and including a second polylactic acid (PLA), the first layer including greater than 0% and less than 30% by weight of polyhydroxyalkanoate (PHA) based on the total weight of the first layer.
[0160] In one embodiment, by including a first layer and a second layer having the specific composition, specifically a first layer including a first polylactic acid (PLA) and a polyhydroxyalkanoate (PHA), and a second layer including a second polylactic acid (PLA) on one side of the first layer, not only can flexibility be improved and noise level be reduced, but also interlayer adhesion properties can be improved due to good interlayer compatibility between the first and second layers, thereby further improving processability and productivity.
[0161] In particular, when the first layer contains more than 0% by weight and less than 30% by weight of polyhydroxyalkanoate (PHA) based on the total weight of the first layer, it is possible to improve flexibility while maintaining appropriate strength, further improve optical properties, and provide a laminate with low thermal shrinkage at high temperatures of 100°C or higher and small thickness deviation.
[0162] Furthermore, the laminate is biodegradable and completely decomposes when buried, making it environmentally friendly. This makes it possible to utilize the laminate in a wider variety of fields and to exhibit excellent properties, which is of technical significance.
[0163] Referring to FIG. 1, a laminate 1 according to an embodiment of the present invention includes a first layer 12 and a second layer 11 disposed on one side of the first layer 12 .
[0164] A laminate according to another embodiment of the present invention may include a first layer, a second layer disposed on one side of the first layer, and a corona layer, a coating layer, or both, disposed on the other side of the first layer.
[0165] 2, the laminate 1 may include a first layer 12, a second layer 11 disposed on an upper surface of the first layer 12, and a corona layer 13 disposed on a lower surface of the first layer 12. In this case, a coating layer may be disposed instead of the corona layer disposed on the lower surface of the first layer 12.
[0166] Also, referring to FIG. 3, the laminate 1 may include a first layer 12, a second layer 11 disposed on an upper surface of the first layer 12, a corona layer 13 disposed on a lower surface of the first layer 12, and a coating layer 14 disposed on the lower surface of the corona layer 13. Each layer of the laminate according to the embodiment will now be described in detail.
[0167] -First layer- According to one implementation, the first layer includes a first polylactic acid (PLA) and a polyhydroxyalkanoate (PHA).
[0168] The first polylactic acid (PLA) may be the same as the polylactic acid (PLA) mentioned in the biaxially stretched film.
[0169] The first layer contains the first polylactic acid (PLA) and polyhydroxyalkanoate (PHA), which not only improves flexibility and reduces noise, but also has good interlayer compatibility with the second layer containing the second polylactic acid (PLA), thereby maintaining excellent interlayer adhesion properties and further improving processability and productivity.
[0170] If the first layer contains only one of the resins polylactic acid (PLA) and polyhydroxyalkanoate (PHA), or neither of them, it is difficult to achieve a satisfactory noise reduction effect or flexibility. In addition, the compatibility between the first layer and the second layer in the laminate may decrease, resulting in poor interlayer adhesion properties or detachment from each other, which may adversely affect processability and productivity.
[0171] The first polylactic acid (PLA) may have a weight average molecular weight (Mw) of 100,000 to 1,000,000 g / mol, for example, 100,000 to 800,000 g / mol, 100,000 to 500,000 g / mol, or 100,000 to 300,000 g / mol. The weight average molecular weight (Mw) may be measured by gel permeation chromatography (GPC). When the weight average molecular weight (Mw) of the first polylactic acid (PLA) is outside the above range, the mechanical strength and heat resistance of the laminate may be further improved.
[0172] The first polylactic acid (PLA) may include L-lactic acid, D-lactic acid, DL-lactic acid, or a combination thereof. Specifically, the first polylactic acid (PLA) may be a random copolymer of L-lactic acid and D-lactic acid. In this case, the content of the L-lactic acid may be 80% by weight to 99% by weight, 83% by weight to 99% by weight, or 85% by weight to 99% by weight based on the total weight of the first polylactic acid.
[0173] The first polylactic acid (PLA) may have a melting temperature (Tm) of 100°C to 250°C, 110°C to 220°C, or 120°C to 200°C.
[0174] The first polylactic acid (PLA) may have a glass transition temperature (Tg) of 30°C to 80°C, 40°C to 80°C, 40°C to 70°C, or 45°C to 65°C.
[0175] The first polylactic acid (PLA) may comprise, based on the total weight of the first layer, more than 70% by weight, 75% by weight or more, 80% by weight or more, 85% by weight or more, 88% by weight or more, 90% by weight or more, 93% by weight or more, or 95% by weight or more. The first polylactic acid (PLA) may comprise, based on the total weight of the first layer, less than 100% by weight, 99% by weight or less, 98% by weight or less, 97% by weight or less, or 95% by weight or less.
[0176] Specifically, the first polylactic acid (PLA) may be included in an amount of more than 70% to less than 100% by weight, more than 70% to 99% by weight, 75% to 99% by weight, 75% to 98% by weight, 75% to 97% by weight, 80% to 97% by weight, 85% to 97% by weight, 90% to 97% by weight, 95% to less than 100% by weight, 95% to 97% by weight, or 90% to 95% by weight, based on the total weight of the first layer.
[0177] If the content of the first polylactic acid (PLA) is too low, the tensile strength of the laminate may decrease, the heat shrinkage rate may increase, and the optical properties such as transparency and light transmittance may decrease. On the other hand, if the content of the first polylactic acid (PLA) is too high, the brittleness may increase, the flexibility may decrease, and the laminate may be easily broken or cracked, and may be noisy.
[0178] In particular, the first polylactic acid (PLA) has a characteristic that the film becomes hard when the operating temperature range is below 20°C due to its high brittleness, and when the film is subjected to impact in winter, it tends to easily crack or break. When the operating temperature range is above 35°C, the film tends to lose elasticity and become soft, and is noisy, so its use is limited.
[0179] Therefore, in the embodiment, the first polylactic acid (PLA) is mixed with polyhydroxyalkanoate (PHA), which has excellent flexibility and low noise.
[0180] In particular, the content of polyhydroxyalkanoate (PHA) in the first layer is important in order to achieve excellent strength, flexibility, improved optical properties, thermal properties, and improved noise level of the laminate.
[0181] According to an implementation example, the first layer may include greater than 0% and less than 30% by weight of polyhydroxyalkanoate (PHA), based on the total weight of the first layer.
[0182] Specifically, the first layer may contain the polyhydroxyalkanoate (PHA) in an amount of more than 0 wt% to less than 30 wt%, more than 0 wt% to less than 25 wt%, more than 0 wt% to less than 20 wt%, 1 wt% to less than 30 wt%, 1 wt% to 25 wt%, 2 wt% to 25 wt%, 2 wt% to 20 wt%, 3 wt% to 25 wt%, 3 wt% to 20 wt%, 3 wt% to 15 wt%, 3 wt% to 10 wt%, more than 0 to 5 wt%, 3 wt% to 5 wt%, or 5 wt% to 10 wt%, based on the total weight of the first layer.
[0183] If the content of the polyhydroxyalkanoate (PHA) is too high, the tensile strength may decrease, the heat shrinkage rate and thickness deviation may increase, the extrusion processability may decrease, and the optical properties may decrease, whereas if the content of the polyhydroxyalkanoate (PHA) is too low, the brittleness may increase, the flexibility may decrease, the material may be easily broken or cracked, and the noise level may increase.
[0184] According to an embodiment, the mixing weight ratio of the first polylactic acid (PLA) to the polyhydroxyalkanoate (PHA) may be more than 70 to less than 100: more than 0 to less than 30, for example, 80 to 97: 3 to 20, for example, 80 to 95: 5 to 20, for example, 90 to 97: 3 to 10, for example, 90 to 95: 5 to 10, or for example, 95 to 97: 3 to 5. When the mixing weight ratio of the first polylactic acid (PLA) to the polyhydroxyalkanoate (PHA) satisfies the above range, it is possible to improve flexibility while maintaining appropriate strength, improve optical properties and thermal properties, and reduce noise level.
[0185] According to a realization example, said polyhydroxyalkanoate (PHA) can be the same as the polyhydroxyalkanoate (PHA) mentioned in said biaxially stretched film.
[0186] Specifically, the copolymerized polyhydroxyalkanoate (PHA) may be a polyhydroxyalkanoate (PHA) with a controlled degree of crystallinity (crystallinity).
[0187] For example, the copolymerized polyhydroxyalkanoate (PHA) may be a copolymerized polyhydroxyalkanoate (PHA) having controlled crystallinity, including a copolymerized polyhydroxyalkanoate containing at least one unit of the chemical formula 1 and at least one unit of the chemical formula 2.
[0188] The polyhydroxyalkanoate (PHA) may be a polyester containing only the units of the chemical formula 1 and the units of the chemical formula 2 as polymerized units, or may contain the units of the chemical formula 1 and the units of the chemical formula 2 as polymerized units, and may further contain different polymerized units other than the above. Also, the units of the chemical formula 2 may be repeated randomly.
[0189] The polyhydroxyalkanoate (PHA) with controlled crystallinity may be one in which the crystallinity and amorphousness are controlled by increasing the irregularity in the molecular structure, and specifically, the type of monomer, the ratio of monomers, or the type and / or content of isomers may be adjusted.
[0190] According to an embodiment, the polyhydroxyalkanoate (PHA) is a copolymerized polyhydroxyalkanoate (PHA) containing a unit of the chemical formula 1 and a unit of the chemical formula 2, and the content of the unit of the chemical formula 2 may be 1 wt % or more, 3 wt % or more, 5 wt % or more, 10 wt % or more, and 60 wt % or less, 55 wt % or less, or 50 wt % or less, based on the total weight of the copolymerized polyhydroxyalkanoate (PHA).
[0191] For example, the polyhydroxyalkanoate (PHA) may be a copolymerized polyhydroxyalkanoate (PHA) containing units of the chemical formula 1 and units of the chemical formula 2, and the content of the units of the chemical formula 2 may be 1 to 60% by weight, 5 to 50% by weight, 10 to 60% by weight, 10 to 50% by weight, 15 to 60% by weight, 15 to 50% by weight, 20 to 60% by weight, 20 to 50% by weight, 25 to 60% by weight, 25 to 50% by weight, 30 to 60% by weight, 30 to 50% by weight, 35 to 60% by weight, 35 to 50% by weight, 40 to 60% by weight, 40 to 50% by weight, 45 to 60% by weight, 45 to 50% by weight, or 46 to 50% by weight.
[0192] According to the implementation, the polyhydroxyalkanoate (PHA) may include isomers. For example, the polyhydroxyalkanoate (PHA) may include structural isomers, enantiomers, or geometric isomers. Specifically, the polyhydroxyalkanoate (PHA) may include structural isomers.
[0193] According to a realization example, the copolymerized polyhydroxyalkanoate (PHA) can be an amorphous polyhydroxyalkanoate (PHA).
[0194] When the copolymerized polyhydroxyalkanoate (PHA) is an amorphous polyhydroxyalkanoate (PHA), the optical properties of the laminate can be improved compared to when a crystalline polyhydroxyalkanoate (PHA) is used as the polyhydroxyalkanoate (PHA) and mixed with the first polylactic acid (PLA) to form the first layer.
[0195] When the copolymerized polyhydroxyalkanoate (PHA) is an amorphous polyhydroxyalkanoate (PHA), the amorphous polyhydroxyalkanoate (PHA) is a copolymerized polyhydroxyalkanoate (PHA) containing units of the chemical formula 1 and units of the chemical formula 2, and may contain 15 to 60% by weight of units of the chemical formula 2 based on the total weight of the copolymerized polyhydroxyalkanoate (PHA).
[0196] In the polyhydroxyalkanoate (PHA), the amorphousness can increase as the content of the unit of Chemical Formula 2 increases, so in the first layer according to the embodiment, the content of the unit of Chemical Formula 2 in the amorphous polyhydroxyalkanoate (PHA) can be important.
[0197] For example, the amorphous polyhydroxyalkanoate (PHA) may contain the unit of Chemical Formula 2 in an amount of 15 to 55 wt%, 15 to 50 wt%, 20 to 60 wt%, 20 to 50 wt%, 25 to 60 wt%, 25 to 50 wt%, 30 to 60 wt%, 30 to 50 wt%, 35 to 60 wt%, 35 to 50 wt%, 40 to 60 wt%, 40 to 50 wt%, 45 to 60 wt%, 45 to 50 wt%, or 46 to 50 wt%, based on the total weight of the polyhydroxyalkanoate (PHA).
[0198] The first layer contains the units of formula 2 in the above range, and thus when polyhydroxyalkanoate (PHA) is mixed with first polylactic acid (PLA), there is compatibility between the resins, which is advantageous in that the optical properties of the laminate can be further improved. If the units of formula 2 in polyhydroxyalkanoate (PHA) are less than 15% by weight, the compatibility between the resins is poor, and the transparency and light transmittance of the laminate may decrease, and the modulus and noise level may decrease.
[0199] According to an embodiment, the amorphous polyhydroxyalkanoate (PHA) is a copolymerized polyhydroxyalkanoate (PHA) containing 3-hydroxybutyrate (3-HB) units and 4-hydroxybutyrate (4-HB) units, and the 4-hydroxybutyrate (4-HB) units may be contained in an amount of 15 to 60 wt % based on the total weight of the copolymerized polyhydroxyalkanoate (PHA).
[0200] In the polyhydroxyalkanoate (PHA), the amorphousness increases as the content of the 4-hydroxybutyrate (4-HB) unit increases, so in the first layer according to the embodiment, the content of the 4-hydroxybutyrate (4-HB) unit in the amorphous polyhydroxyalkanoate (PHA) may be important.
[0201] For example, the 4-hydroxybutyrate (4-HB) units may be contained in an amount of, for example, 20 to 60% by weight, for example, 25 to 60% by weight, for example, 25 to 50% by weight, for example, 30 to 60% by weight, for example, 30 to 50% by weight, for example, 35 to 60% by weight, for example, 35 to 50% by weight, for example, 40 to 60% by weight, for example, 40 to 50% by weight, for example, 45 to 60% by weight, for example, 45 to 50% by weight, for example, 46 to 60% by weight, or for example, 46 to 50% by weight, based on the total weight of the copolymerized polyhydroxyalkanoate (PHA).
[0202] The first layer contains 4-hydroxybutyrate (4-HB) units in the above range, and when polyhydroxyalkanoate (PHA) is mixed with the first polylactic acid (PLA), the resins are compatible with each other, which has the advantage of further improving the optical properties of the laminate. If the 4-hydroxybutyrate (4-HB) units are less than 15% by weight, the compatibility between the resins will be poor and the optical properties of the laminate will be reduced.
[0203] The polyhydroxyalkanoate (PHA) may be a polyester containing only 3-hydroxybutyrate units (3-HB) and 4-hydroxybutyrate units (4-HB) as polymerized units (i.e., the polymerized units consist of only 3-hydroxybutyrate units (3-HB) and 4-hydroxybutyrate units (4-HB)), or may contain 3-hydroxybutyrate units (3-HB) and 4-hydroxybutyrate (4-HB) units as polymerized units, and may further contain different polymerized units other than those mentioned above. In addition, the 4-hydroxybutyrate (4-HB) units may be repeated randomly.
[0204] The different polymerized units include lactate (LA), glycolate (GA), 3-hydroxypropionate (3HP), 3-hydroxyvalerate (3HV), 5-hydroxyvalerate (5HV), 5-hydroxyhexanoate (5HH), 6-hydroxyhexanoate (6HH), 3-hydroxyhexanoate (3HH), or hydroxyalkanoates having 7 or more carbon atoms.
[0205] The weight average molecular weight (Mw) and glass transition temperature (Tg) of the polyhydroxyalkanoate (PHA) are as described above.
[0206] According to one implementation, the first layer may further include a filler. The filler may include an organic filler, an inorganic filler, or a mixture thereof.
[0207] The organic filler may include an organic filler comprising a material selected from hard acrylate, polystyrene, nylon, and soft acrylate.
[0208] The inorganic filler may be one or more selected from the group consisting of barium sulfate, silica, and calcium carbonate. The filler may be an inorganic filler and may include, for example, silica.
[0209] By including the filler, the first layer can have excellent slip properties and improve processability, thereby providing excellent quality.
[0210] The particle size of the filler may be 0.1 μm to 6.0 μm. For example, the particle size of the filler may be 1.0 μm to 5.5 μm or 2.0 μm to 5.2 μm.
[0211] The first layer may contain the filler in an amount of 0.01 to 3 wt % based on the total weight of the first layer. For example, the first layer may contain the filler in an amount of 0.01 to 2.5 wt %, 0.01 to 2 wt %, 0.01 to 1.5 wt %, 0.01 to 1 wt %, 0.01 to 0.5 wt %, or 0.01 to 0.2 wt % based on the total weight of the first layer.
[0212] The thickness of the first layer may be, for example, 1 μm to 20 μm, for example, 2 μm to 19 μm, or for example, 3 μm to 17 μm.
[0213] -Second layer- According to one implementation, the second layer is disposed on one side of the first layer and includes a second polylactic acid (PLA).
[0214] Since the second layer contains the second polylactic acid (PLA), it has good compatibility with the first layer containing the first polylactic acid (PLA) and polyhydroxyalkanoate (PHA), and therefore can maintain excellent interlayer adhesion properties, thereby further improving processability and productivity.
[0215] If the second layer does not contain the second polylactic acid (PLA) but contains another resin such as polytriethylene terephthalate (PTT), the interlayer compatibility between the first layer and the second layer will be poor, which may result in poor interlayer adhesion properties or separation from each other, resulting in adverse effects on processability and productivity.
[0216] The second layer may include an isomer of the second polylactic acid. The second layer may include the L-isomer, D-isomer, DL-isomer, or mixtures thereof of the second polylactic acid. For example, the second polylactic acid (PLA) may be a random copolymer of L-lactic acid and D-lactic acid.
[0217] Specifically, the second polylactic acid may include L-isomer and D-isomer stereoisomers having opposite configurations, and such stereoisomers may be symmetrical to each other in that they have the same chemical structure and physical properties but only the configuration is a mirror image.
[0218] When the second layer contains a mixture of the L-isomer and the D-isomer of the second polylactic acid, the transparency of the film is improved and the film has thermal adhesion properties, making it useful for thermal adhesion applications.
[0219] According to an embodiment, the second layer may contain 5% to 30% by weight of the D-isomer based on the total weight of the second polylactic acid. If the content of the D-isomer is too high, the thickness deviation and heat shrinkage of the laminate may increase, and physical properties of the laminate such as tensile strength may decrease, and in the process, the winding property may be insufficient during production and processing, causing problems with the roll pass, resulting in reduced processability and productivity. On the other hand, if the content of the D-isomer is too low, a large amount of heat is required during the thermal bonding process, and the shape of the laminate may be deformed, such as the film undulating when the laminate is formed into a film.
[0220] According to an embodiment, the second layer comprises a mixture of L-isomer and D-isomer of the second polylactic acid, and the weight ratio of the L-isomer and D-isomer can be 70-95:5-30.
[0221] For example, the second layer may contain poly-L-lactic acid (L-PLA) and poly-D-lactic acid (D-PLA), where the weight ratio of the L-PLA and D-PLA (L-PLA:D-PLA) may be 70-95:5-30, for example 72-95:5-28, for example 74-93:7-26, or for example 75-93:7-25.
[0222] When the weight ratio of the L-isomer and the D-isomer satisfies the above range, the optical properties of the film can be improved, the thermal adhesion performance can be further improved, and the thickness deviation and the thermal shrinkage rate of the laminate can be reduced, and physical properties such as tensile strength and modulus can be improved, thereby improving processability and productivity.
[0223] The second polylactic acid (PLA) may have a weight average molecular weight (Mw) of, for example, 50,000 to 1,000,000 g / mol, for example, 50,000 to 800,000 g / mol, for example, 50,000 to 500,000 g / mol, for example, 50,000 to 300,000 g / mol. The weight average molecular weight (Mw) may be measured by gel permeation chromatography (GPC). When the weight average molecular weight (Mw) of the second polylactic acid (PLA) is outside the above range, the mechanical strength and heat resistance of the laminate may be further improved.
[0224] The second polylactic acid (PLA) may have a melting temperature (Tm) of, for example, 100° C. to 250° C., 110° C. to 220° C., or 120° C. to 200° C. In addition, the second polylactic acid (PLA) may not have a melting temperature (Tm).
[0225] The second polylactic acid (PLA) may have a glass transition temperature (Tg) of 20°C to 80°C, 25°C to 80°C, 30°C to 75°C, or 35°C to 70°C.
[0226] On the other hand, the second layer may further comprise a filler to improve the slip characteristics.
[0227] The filler may be the same or different in type and content from the filler in the first layer. Specifically, the particle size of the filler contained in the second layer may be 0.1 μm to 6.0 μm. The second layer may contain the filler in an amount of 0.01 to 3% by weight based on the total weight of the second layer.
[0228] When the second layer contains a filler, the slipperiness is improved in the process, and processing can be made easier.
[0229] The thickness of the second layer may be, for example, 0.1 μm to 20 μm, for example, 0.1 μm to 18 μm, or for example, 0.1 μm to 16 μm.
[0230] Meanwhile, the thickness ratio of the first layer and the second layer may be, for example, 1:0.1-1, for example, 1:0.1-0.9, or, for example, 1:0.1-0.8.
[0231] -Corona layer- According to an embodiment, the laminate may further include a corona layer disposed on the other side of the first layer. Specifically, the corona layer may be formed directly on the other side of the first layer.
[0232] By further including a corona layer, the laminate can remove oily contaminants from the surface of the laminate, form a surface that is compatible with the adhesive site, and increase adhesive strength. The surface can be chemically and physically modified to further improve hydrophilicity, adhesiveness, printability, coating properties, deposition properties, and the like.
[0233] Specifically, the first layer of the laminate has very little polarity and high crystallinity due to the absence of polar groups, and therefore may have low affinity for inks and adhesives. To this end, a high frequency and high voltage can be applied to the surface of the first layer to cause dielectric breakdown of molecular bonds on the surface, generating polar groups on the surface and increasing surface energy.
[0234] The corona layer is formed by corona treatment of the first layer and may include polar functional groups selected from the group consisting of -CO, -COOH, and -OH.
[0235] The first layer has a surface tension with respect to the corona-treated surface of 38 dyn / cm or more, for example, 38 to 70 dyn / cm, for example, 38 to 68 dyn / cm, or for example, 38 to 66 dyn / cm. When the surface tension of the first layer with respect to the corona-treated surface satisfies this range, the adhesion, printability, coating properties, deposition properties, etc. of the laminate can be further improved.
[0236] The thickness of the corona layer can be appropriately adjusted depending on the use and purpose of the laminate, and specifically can be, for example, 0.1 nm to 1000 nm, for example, 0.2 nm to 900 nm, or for example, 0.1 nm to 800 nm, but is not limited thereto.
[0237] -Coating layer- The laminate according to one implementation may further include a coating layer disposed on the other side of the first layer.
[0238] The coating layer may include a primer coating layer, which may improve antistatic performance.
[0239] The primer coating layer may be on the other side of the first layer, or if the laminate includes the corona layer, the corona layer may be on the other side of the first layer and the primer coating layer may be on the other side (lower side) of the corona layer.
[0240] Specifically, a primer coating layer may be formed by applying a primer treatment to the other surface of the first layer, or a primer coating layer may be formed by applying a primer treatment to the other surface (lower surface) of the corona layer disposed on the other surface of the first layer.
[0241] The primer coating layer may contain one or more compounds selected from the group consisting of ammonium-based compounds, phosphoric acid-based compounds, and polymers such as acrylic resins and urethane resins, each of which has antistatic properties.
[0242] The surface resistance of the primer coating layer may be 0.1 to 30 Ω / □, 0.2 to 28 Ω / □, 0.3 to 26 Ω / □, 0.4 to 24 Ω / □, or 1 to 20 Ω / □.
[0243] The surface resistance is, for example, a value obtained by evaluating antistatic performance using a surface resistance measuring device at room temperature (22±2° C.) and relative humidity (60%±10%).
[0244] The thickness of the coating layer can be appropriately adjusted depending on the use and purpose of the laminate, and can be specifically, but is not limited to, 15 nm to 50 nm, 20 nm to 45 nm, 25 nm to 40 nm, or 30 nm to 35 nm.
[0245] A laminate of implementations of the present invention may include a multi-layer structure of two or more layers, such as three or more layers, such as four or more layers.
[0246] -Physical properties of laminate- According to one embodiment, when the thickness of the laminate is 19 to 22 μm, the laminate may have a composite soft noise number (LSN) represented by the following formula 2-1 of 18 or less.
[0247] <Formula 2-1> Flexible noise composite index (LSN) = N AVG ×LS In the above formula 2-1, N AVG is the average sound level (dB) calculated by measuring the maximum sound level five times for each test piece of laminated material, when a class 2 sound level meter specified in KS C IEC61672-1 is aimed toward the noise source and a test piece of laminated material with a width of 21 cm and a length of 29.5 cm is repeatedly crumpled and unfolded 10 times for 10 seconds at a height of 1.2m to 1.5m from the ground. The unit is not included. The LS is a loop stiffness (gf) measured based on ASTM D747 by fixing a loop-shaped laminate test piece having a width of 1.5 cm and a length of 18 cm to a loop stiffness tester and measuring the load at the center of the loop, and is a numerical value without a unit.
[0248] The composite flexible noise index (LSN) represented by the formula 2-1 is the product of the average sound intensity and the loop stiffness of the laminate, which is an index showing the degree of the composite characteristics of the flexibility and sound intensity of the laminate. Therefore, the composite flexible noise index (LSN) can be a measure of the quality of a molded product such as a packaging material containing the laminate.
[0249] The soft noise composite index (LSN) is the average noise intensity of the first layer (N AVG) is lower, and noise level (N AVG The soft noise composite index (LSN) may be higher when the loop stiffness (LS) is higher. Also, the soft noise composite index (LSN) may be lower when the loop stiffness (LS) is lower, and higher when the loop stiffness (LS) is higher.
[0250] When the soft noise composite index (LSN) having such characteristics satisfies the above-mentioned specific range or less, the laminate has excellent mechanical properties, optical properties and thermal properties, and can reduce noise intensity.
[0251] Specifically, the laminate may have a flexibility noise composite index (LSN) of, for example, 18 or less, 17 or less, 16 or less, or 15 or less. If the flexibility noise composite index (LSN) of the laminate exceeds 18, the flexibility may decrease and the brittleness may increase, and the noise may increase, so that the quality may decrease when applied to a packaging material.
[0252] The composite soft noise index (LSN) of the laminate may be the same or different depending on the machine direction (MD) and the transverse direction (TD) of the laminate, where the machine direction (MD) of the laminate refers to the length direction or machine direction, and the transverse direction (TD) of the laminate refers to the width direction as a direction perpendicular to the machine direction (MD).
[0253] Specifically, the composite soft noise index (LSN) of the laminate in the machine direction (MD) MD ) can be, for example, 4 to 18, 5 to 18, 5 to 17, 6 to 17, 8 to 17, or 8 to 16.
[0254] The laminate's transverse (TD) flexibility noise composite index (LSN TD ) can be, for example, 4 to 18, 5 to 17, 5 to 16, 6 to 16, 8 to 15, or 9 to 15.
[0255] The laminate includes the LSN MD Only satisfied or LSN TD Only LSN may be satisfied MD and LSN TDIn this case, the laminate according to the embodiment can improve flexibility while maintaining an appropriate tensile strength, and can reduce noise, which is more advantageous in achieving the intended effect, and therefore can provide an environmentally friendly packaging material with excellent quality.
[0256] On the other hand, in the formula 2-1, the average noise intensity (N AVG ) was measured using a sound level meter of class 2 or higher as specified in KS C IEC61672-1, facing the direction of the noise source, at a point 1.2m to 1.5m above the ground, when the laminate was repeatedly crumpled and unfolded 10 times at a constant speed for 10 seconds, and the maximum sound level was recorded. This was repeated 5 times each, and the average value of the maximum sound levels for each time was calculated and defined as the average sound level. The sound level can be measured at a height of 1.2m to 1.5m above the ground, and if there is an obstacle over 1.5m high at the measurement point, it can be measured at a point about 1.0m to 3.5m away from the obstacle in the direction of the noise source.
[0257] The laminate has an average noise intensity (N AVG ) is preferable in terms of providing a high-quality packaging material.
[0258] Specifically, the average noise intensity (N AVG ) may be, for example, 86 dB or less, for example, 85 dB or less, for example, 84.8 dB or less, or for example, 84 dB or less.
[0259] The average noise intensity of the laminate (N AVG ) is 86 dB or less, it is advantageous in controlling the soft noise composite index (LSN) of the above formula 2-1 to 18 or less, and it is possible to provide a packaging material of good quality by improving noise.
[0260] In addition, in the formula 2-1, the loop stiffness (LS) of the laminate is measured based on ASTM D747 by fixing a loop-shaped laminate test piece having a width of 1.5 cm and a length of 18 cm to a loop stiffness tester (manufactured by Toyo Seiki Seisakusho) and measuring the load at the center of the loop, and is an index showing the degree of flexibility of the laminate.
[0261] The loop stiffness (LS) of the laminate may be 0.20 gf or less, or 0.19 gf or less. Specifically, the loop stiffness (LS) of the laminate may be, for example, 0.10 to 0.20 gf, for example, 0.10 to 0.19 gf, for example, 0.10 to 0.18 gf, or for example, 0.10 to 0.17 gf.
[0262] A lower loop stiffness (LS) of the laminate may increase flexibility, and a higher loop stiffness (LS) of the laminate may decrease flexibility.
[0263] Additionally, the loop stiffness (LS) of the laminate may be the same or different in the machine direction (MD) and transverse direction (TD) of the laminate.
[0264] Specifically, the loop stiffness (LS) of the laminate in the machine direction (MD) MD ) may be, for example, 0.10 to 0.20 gf, for example, 0.10 to 0.19 gf, for example, 0.11 to 0.19 gf, for example, 0.11 to 0.18 gf, or for example, 0.11 to 0.15 gf.
[0265] The loop stiffness (LS) of the laminate in the transverse direction (TD) TD ) may be, for example, 0.10 to 0.20 gf, for example, 0.10 to 0.18 gf, for example, 0.10 to 0.17 gf, or for example, 0.12 to 0.16 gf.
[0266] The laminate is MD Only satisfied with LS TD Only LS may be satisfied MD and L.S. TDIn this case, the laminate according to the embodiment is more effective in controlling the soft noise composite index (LSN) represented by the formula 2-1 within the above range, and is therefore more advantageous in achieving the intended effect, so that an environmentally friendly packaging material with excellent quality can be provided.
[0267] On the other hand, the laminate has a thermal shrinkage rate (S 100 ) may be 15% or less.
[0268] <Formula 2-2> Heat shrinkage rate (S 100 )(%)={(L 25 -L 100 ) / L 25}×100 In the above formula 2-2, L 25 is the initial length (mm) of the laminate test piece at 25°C, L 100 is the length (mm) of a laminate test piece measured immediately after being held in a hot air blower at 100° C. for 5 minutes.
[0269] The thermal shrinkage rate (S 100 ) is a value obtained by converting the degree of thermal shrinkage of a laminate test piece into a percentage when exposed to hot air at a temperature of 100°C, and is a value calculated as a percentage of the change in the initial length of the laminate test piece relative to the initial length of the laminate test piece and the change in the length of the laminate test piece measured immediately after being retained in the hot air blower for 5 minutes.
[0270] The heat shrinkage rate (S 100 ) can be calculated by cutting the laminate into test pieces of 150 mm length and 2 cm width regardless of the direction, and then measuring the initial length at room temperature and the length of the laminate test piece after being left in a hot air oven at 100°C for 5 minutes.
[0271] The heat shrinkage rate (S 100 ) may be 15% or less, 12% or less, 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, or 4.5% or less.
[0272] The heat shrinkage rate (S100 When the above range is satisfied, the degree of thermal shrinkage at high hot air temperatures of 100° C. or more is small, and the thermal properties are improved, leading to further improved printability and moldability.
[0273] The thermal shrinkage rate (S 100 ) may be the same or different in the machine direction (MD) and transverse direction (TD) of the laminate.
[0274] Specifically, the thermal shrinkage rate (S MD100 ) can be 15% or less, 12% or less, 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, 4.7% or less, or 4.5% or less.
[0275] The thermal shrinkage rate (S TD100 ) can be, for example, 15% or less, 12% or less, 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, 5.5% or less, or 5.0% or less.
[0276] If the thermal shrinkage ratios of the laminate in the machine direction (MD) and the transverse direction (TD) exceed the above ranges, problems will arise in printing due to severe shrinkage in the machine direction and the transverse direction caused by hot air during printing and lamination, and curling will occur severely after printing, resulting in a phenomenon in which the laminate is rolled up, which is undesirable.
[0277] Meanwhile, the laminate according to the embodiment may have a forming index (FI) represented by the following formula 2-3 of 65 or more.
[0278] <Formula 2-3> Forming index (FI)=TS / LS In the above formula 2-3, TS is a tensile strength (kgf / mm) measured at room temperature using a universal testing machine (UTM). 2 ) without units, and LS is as defined above.
[0279] The forming index (FI) of the laminate is the ratio of the tensile strength to the loop stiffness of the laminate and can provide a measure of whether the tensile strength and flexibility are adequate.
[0280] That is, according to the embodiment, one of the main features of the laminate is that it has increased flexibility and soft properties while maintaining an appropriate range of strength, for example, tensile strength. In this case, the laminate has excellent moldability and can be advantageous for various application expansions.
[0281] The forming index (FI) of the laminate may be, for example, 65 or more, 68 or more, 70 or more, 73 or more, 75 or more, 80 or more, 85 or more, 88 or more, 90 or more, 95 or more, or 100 or more. Specifically, the forming index (FI) of the laminate may be, for example, 65 to 120, for example, 65 to 110, or for example, 65 to 105. If the forming index (FI) of the laminate is less than 65, the flexibility may be reduced and the laminate may be easily broken, or the strength may be reduced and various problems may occur during processing or molding, and there may be limitations in the application of the laminate to various uses, and the quality of molded products such as packaging materials to which the laminate is applied may be reduced or defects may occur.
[0282] The forming index A (FI) of the laminate may be the same or different in the machine direction (MD) and transverse direction (TD) of the laminate.
[0283] Specifically, the forming index (FI) of the laminate in the machine direction (MD) MD ) may be, for example, 65 to 120, for example, 65 to 100, for example, 65 to 90, or for example, 70 to 90.
[0284] The forming index (FI) of the laminate in the transverse direction (TD) TD ) may be, for example, 70 to 120, for example, 72 to 110, for example, 80 to 110, for example, 90 to 110, or for example, 90 to 105.
[0285] The laminate is MD Only satisfied or FI TDMay only satisfy FI MD and FI TD In this case, the laminate according to the embodiment can improve flexibility while maintaining an appropriate tensile strength, and can provide an environmentally friendly packaging material with excellent quality.
[0286] In addition, in the formula 2-3, the loop stiffness (LS) of the laminate is as defined above.
[0287] In addition, the tensile strength of the laminate can be measured by preparing a laminate test piece according to ASTM D882, cutting it to a length of 100 mm and a width of 15 mm, mounting it so that the length between chucks is 50 mm, and testing it at a room temperature of 25° C. at a tensile speed of 200 mm / min using an Instron universal testing machine (UTM, model name 5966), and then measuring the tensile strength using a program built into the machine.
[0288] The tensile strength is, for example, 7 to 20 kgf / mm 2 , for example 8~20kgf / mm 2 , for example 8~18kgf / mm 2 , for example 9~17kgf / mm 2 , or for example 10 to 17 kgf / mm 2 It could be.
[0289] When the tensile strength satisfies the above range, the productivity, processability and moldability of the laminate can be improved at the same time.
[0290] Additionally, the tensile strength (TS) of the laminate may be the same or different in the machine direction (MD) and transverse direction (TD) of the laminate.
[0291] Specifically, the tensile strength (TS) of the laminate in the machine direction (MD) MD ) is, for example, 7 to 14 kgf / mm 2 , for example 8~14kgf / mm 2 , for example 9~14kgf / mm 2 , for example 10~14kgf / mm 2 , or for example 11 to 14 kgf / mm 2It could be.
[0292] The tensile strength (TS) of the laminate in the transverse direction (TD) TD ) is, for example, 8 to 20 kgf / mm 2 , for example 10~20kgf / mm 2 , for example 11 to 20 kgf / mm 2 , for example 12~18kgf / mm 2 , or for example 13 to 17 kgf / mm 2 It could be.
[0293] The laminate is MD Only satisfied with the TS TD Only TS may be satisfied MD and T.S. TD In this case, the laminate according to the embodiment can control the moldability index (FI) represented by the above formula 2-3 within the above range, so that the productivity, processability, and moldability can be improved simultaneously, and an environmentally friendly packaging material with excellent quality can be provided.
[0294] On the other hand, the laminate has a stress-strain curve of 200 kgf / mm 2 ~380kgf / mm 2 , 230kgf / mm 2 ~380kgf / mm 2 , 250kgf / mm 2 ~350kgf / mm 2 , 280kgf / mm 2 ~350kgf / mm 2 , or 290kgf / mm 2 ~350kgf / mm 2 The modulus is 200 kgf / mm 2 If the modulus is less than 380 kgf / mm, the resistance to mechanical tension during processing such as printing or lamination is insufficient, and wrinkles are generated in the running direction, causing problems in printing, or breakage occurs during running, which is undesirable. 2If the modulus exceeds 100%, the stiffness of the laminate increases and the laminate may easily break or crack due to an external impact. Also, within the above range, the lower the modulus, the more excellent the flexibility.
[0295] Additionally, the modulus of the laminate may be the same or different in the machine direction (MD) and transverse direction (TD) of the laminate.
[0296] Specifically, the modulus (M MD ) is 200kgf / mm 2 ~380kgf / mm 2 , 250kgf / mm 2 ~380kgf / mm 2 , 260kgf / mm 2 ~350kgf / mm 2 , 290kgf / mm 2 ~350kgf / mm 2 , or 295kgf / mm 2 ~345kgf / mm 2 It could be.
[0297] The transverse direction (TD) modulus (M TD ) is, for example, 200 kgf / mm 2 ~380kgf / mm 2 , 260kgf / mm 2 ~380kgf / mm 2 , 270kgf / mm 2 ~350kgf / mm 2 , 280kgf / mm 2 ~350kgf / mm 2 , or 300 kgf / mm 2 ~350kgf / mm 2 It could be.
[0298] The modulus of the laminate in the transverse direction (TD) (M TD ) is the modulus in the machine direction (MD) (M MD ) can be larger than
[0299] Meanwhile, the laminate may have a thickness deviation of 10 μm or less across the entire width of the laminate. Specifically, the laminate may have a thickness deviation of 9 μm or less, 8.5 μm or less, 8 μm or less, 7 μm or less, 6.5 μm or less, 5 μm or less, or 4.7 μm or less across the entire width of the laminate.
[0300] On the other hand, the laminate has excellent interlayer adhesion properties between the first layer and the second layer.
[0301] Specifically, the thermal adhesive strength of the first layer and the second layer is 0.7 to 2.0 kgf / mm 2 Specifically, the thermal adhesive strength of the first layer and the second layer may be 0.7 to 1.8 kgf / mm 2 , 0.9~1.8kgf / mm 2 Or 0.9~1.7kgf / mm 2 It could be.
[0302] When the thermal adhesive strength of the first layer and the second layer is within the above range, the interlayer adhesive properties are excellent, separation of the layers can be prevented, and processability and productivity can be further improved.
[0303] The thermal adhesive strength was evaluated by preparing a laminate test piece based on, for example, ASTM D882, cutting it to a length of about 100 mm and a width of about 15 mm, heat-laminating the opposing first and second layers with a heat seal tester (Tester Sangyo Co., Ltd., TP-701-B), and then mounting the laminate test piece in an Instron universal testing machine (UTM, model name 5966) so that the heat-laminated part of the laminate test piece was in the center and the chuck distance was 50 mm. The first and second layers of the laminate test piece were peeled at an angle of 180° at a tension speed of about 200 mm / min at room temperature of about 25° C., and the strength was measured using a program built into the tension equipment.
[0304] On the other hand, the laminate can have excellent optical properties. Specifically, the laminate may have a haze of 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, or 5% or less. If the haze exceeds the above range, the transparency of the laminate may be significantly reduced, and the use of the laminate in packaging applications where the contents of the contents can be seen may be limited.
[0305] The laminate according to the embodiment may provide a transparent laminate with low haze when it contains a certain content of amorphous polyhydroxyalkanoate (PHA).
[0306] The laminate may have a light transmittance of 90% or more, 92% or more, or 93% or more.
[0307] Furthermore, the laminate has a biodegradability of 90% or more, measured based on the amount of carbon dioxide generated according to KS M3100-1. Biodegradability is the ratio of decomposition to a standard substance (e.g., cellulose) in the same period, and the Ministry of Environment of the Republic of Korea defines a substance as biodegradable when its biodegradability is 90% or more compared to the standard substance.
[0308] The above-mentioned structural and physical property characteristics of the laminate according to the embodiment can be efficiently achieved by manufacturing the laminate according to the embodiment.
[0309] A method for producing the laminate will now be described in detail.
[0310] [Method of manufacturing laminate] According to one embodiment, a method for producing a laminate is provided, the method comprising the steps of: preparing a first resin including a first polylactic acid (PLA) and a polyhydroxyalkanoate (PHA) and a second resin including a second polylactic acid (PLA) (step 1); melt-co-extruding the first resin and the second resin to obtain a two-layer laminated sheet (step 2); and biaxially stretching and heat-setting the laminated sheet to obtain a laminate (step 3), the laminate including a first layer including the first polylactic acid (PLA) and the polyhydroxyalkanoate (PHA) and a second layer disposed on one side of the first layer and including the second polylactic acid (PLA), the first layer including more than 0% by weight and less than 30% by weight of the polyhydroxyalkanoate (PHA) based on the total weight of the first layer.
[0311] A method for producing a laminate according to an embodiment of the present invention involves melt co-extruding a first resin and a second resin having a specific composition to obtain a two-layer laminated sheet, which is then biaxially stretched and heat-set, thereby further improving processability and productivity, and achieving the physical property effects desired in the present invention in an economical and efficient manner.
[0312] Referring to FIG. 1, the method for manufacturing the laminate (S100) may include a step of preparing (S110) a first resin including a first polylactic acid (PLA) and a polyhydroxyalkanoate (PHA) and a second resin including a second polylactic acid (PLA).
[0313] Specifically, the first resin includes a first polylactic acid (PLA) and a polyhydroxyalkanoate (PHA), and the contents or mixing weight ratios thereof are as described above.
[0314] In addition, when the first polylactic acid (PLA) and the polyhydroxyalkanoate (PHA) are mixed, a filler may be further added to improve slipperiness and quality. The type, content, particle size, etc. of the filler are as described above.
[0315] On the other hand, the second resin includes a second polylactic acid (PLA). The second polylactic acid (PLA) is as described above.
[0316] The method for producing the laminate (S100) may include the step of melt-co-extruding the first resin and the second resin to obtain a two-layer laminated sheet (S120).
[0317] During the melt co-extrusion process, the extrusion temperatures of the first resin and the second resin can be adjusted, respectively.
[0318] Specifically, the extrusion temperature of the first resin and the extrusion temperature of the second resin may be the same or different, and the difference between the extrusion temperature of the first resin and the extrusion temperature of the second resin may be 80° C. or less. Specifically, the difference between the extrusion temperature of the first resin and the extrusion temperature of the second resin may be 60° C. or less, 50° C. or less, or 40° C. or less.
[0319] For example, the extrusion temperature of the first resin may be, for example, 180° C. to 250° C., and the extrusion temperature of the second resin may be, for example, 180° C. to 270° C. After the melt extrusion, the resin is brought into contact with a cooling roll cooled to about 10° C. to 40° C. to obtain a two-layer laminated sheet.
[0320] Meanwhile, depending on the implementation, the method may further include a step of drying the first resin and the second resin prior to the melt co-extrusion.
[0321] The drying step may or may not be required depending on the type of extruder.
[0322] For example, when the extruder is a single extruder, melt coextrusion may be performed after the drying step. The drying step may be performed, for example, at 40° C. to 130° C. for 4 hours to 24 hours.
[0323] The method for producing the laminate (S100) may include a step of biaxially stretching and heat setting the laminated sheet to obtain a laminate (S130).
[0324] Specifically, the two-layer laminated sheet can be biaxially stretched, and the biaxial stretching step can include, for example, a step of preheating to 50°C to 80°C, followed by a step of stretching 2 to 4 times in the machine direction (MD) at 40°C to 100°C, and a step of stretching 3 to 5 times in the transverse direction (MD) at 50°C to 110°C.
[0325] By biaxially stretching the laminated sheet in both directions, the physical properties and formability of the laminate can be improved, and a high-quality packaging material can be realized.
[0326] If the laminate is uniaxially stretched in only one of the machine direction and the cross direction, the thickness deviation of the laminate will be large, and the strength of the other side that is not stretched will decrease, and the thermal properties may also decrease.
[0327] The heat fixing step may be carried out at 50°C to 150°C, 70°C to 150°C, 100°C to 150°C, or 120°C to 150°C.
[0328] Meanwhile, the method for manufacturing the laminate (S100) may further include forming a corona layer, a coating layer, or both on the other side of the first layer.
[0329] Specifically, a corona layer may be formed by corona treatment of the first layer.
[0330] In the corona treatment, a corona discharge occurs when a high frequency-high voltage output is applied between a discharge electrode and a treatment roll, and at this time, the corona treatment can be performed by passing a desired surface.
[0331] Specifically, the strength of the corona discharge may be, for example, 3 kW to 20 kW. If the strength of the corona discharge is below this range, the effect of the corona discharge treatment will be minimal, whereas if the strength of the corona discharge is above this range, excessive surface modification may cause surface damage. The constitution and physical properties of the corona layer are as described above.
[0332] Also, a coating layer may be formed on the other surface of the first layer. The coating layer may include a primer coating layer, and the primer coating layer may be formed by primer treating the other surface of the first layer with a primer composition containing one or more selected from the group consisting of ammonium-based compounds, phosphoric acid-based compounds, and polymers such as acrylic resins and urethane resins to form surface roughness and further improve adhesion properties.
[0333] The primer coating layer may be formed on the other side of the first layer, or, if the laminate includes the corona layer, on the other side of the first layer and the primer coating layer may be formed on the other side of the corona layer.
[0334] The primer composition may also contain a curing agent, more specifically, 4,4'-diaminodiphenylmethane (DDM), aromatic diamines, and mixtures thereof. In this case, the amount of the curing agent may be 0.1 to 50% by weight based on the total weight of the primer composition.
[0335] The primer treatment method may be a method commonly used in the art, such as spraying, brushing, rolling, etc. Specifically, the primer composition may be sprayed onto the surface of the first layer using an airless spray under conditions of an induction time of 1 to 30 minutes, a spray pressure of 5 to 500 MPa, a nozzle diameter of 0.46 to 0.58 mm, and a spray angle of 40° to 80°.
[0336] In addition, in order to enhance the adhesiveness of the laminate, a surface treatment such as a plasma treatment, an ultraviolet irradiation treatment, a flame treatment, or a soap treatment may be appropriately carried out.
[0337] Producing the laminate by the manufacturing method of the embodiment may be more effective in producing a laminate having a desired structure and physical properties.
[0338] [Environmentally friendly packaging materials] In one embodiment, an environmentally friendly packaging material can be provided that includes a biaxially stretched film, the biaxially stretched film comprising polylactic acid (PLA) and polyhydroxyalkanoate (PHA), the biaxially stretched film comprising more than 0% by weight and less than 30% by weight of polyhydroxyalkanoate (PHA) based on the total weight of the biaxially stretched film, and when the film has a thickness of 19 μm to 21 μm, the flexible noise composite index (LSN) represented by the above formula 1-1 is 20 or less.
[0339] In another embodiment, an environmentally friendly packaging material may be provided that includes a laminate, the laminate including a first layer including a first polylactic acid (PLA) and a polyhydroxyalkanoate (PHA), and a second layer disposed on one side of the first layer and including a second polylactic acid (PLA), the first layer including more than 0% by weight and less than 30% by weight of polyhydroxyalkanoate (PHA) based on the total weight of the first layer.
[0340] The environmentally friendly packaging material may be in the form of a film that can be used, for example, as a general disposable packaging material or food packaging material, or in the form of a fiber that can be used as a woven fabric, knitted fabric, nonwoven fabric, rope, etc., or in the form of a container that can be used as a food packaging container for lunch boxes, etc.
[0341] The environmentally friendly packaging material has excellent strength and flexibility, and also has excellent optical properties such as transparency, excellent thermal properties, and low noise level, and thus can provide excellent physical properties and quality. In addition, the packaging material is biodegradable and completely decomposed when buried, and has environmentally friendly properties, so that the packaging material can be used in various fields and can exhibit excellent properties.
[0342] (Example) The present invention will be described in more detail with reference to the following examples. The following examples are merely illustrative of the present invention, and are not intended to limit the scope of the present invention.
[0343] [Manufacturing of biaxially oriented films] (Example 1-1) A polylactic acid (PLA) resin (NatureWorks, USA), which is a random copolymer of L-lactic acid and D-lactic acid (L-lactic acid content: 98% by weight), has a weight average molecular weight of 150,000 g / mol, a melting temperature (Tm) of 170° C., and a glass transition temperature (Tg) of 58° C., an amorphous polyhydroxyalkanoate (PHA) resin (CJ, Korea) with a glass transition temperature (Tg) of −30° C., and silica (Fuji Silysia Chemical, 3.9 μm) were mixed to produce a mixed resin. In this case, the polylactic acid (PLA) and the amorphous polyhydroxyalkanoate (PHA) were mixed so that the weight ratio of the polylactic acid (PLA) and the amorphous polyhydroxyalkanoate (PHA) in the final film was 97:3, as shown in Table 1 below, and the content of silica was 0.1% by weight based on the total weight of the biaxially stretched film.
[0344] The mixed resin was melt-extruded through an extruder at a temperature of 220° C., and then brought into contact with a cooling roll cooled to 20° C. to obtain a sheet.
[0345] The sheet thus obtained was immediately preheated to 55° C. and then stretched 3 times in the machine direction (MD) by passing it through rolls in a stretching section at 70° C. The stretched film was stretched 4 times in the transverse direction (TD) in the stretching section of a tenter divided into two sections, the average temperature of which was 85° C. in the initial 30% section and 100° C. in the latter 70% section.
[0346] The stretched sheet was then heat-set at 150° C. in the heat treatment section of the tenter to produce a biaxially stretched film having a thickness of 19.98 μm.
[0347] (Example 1-2) As shown in Table 1 below, in the final biaxially stretched film, the same procedure as in Example 1-1 was carried out, except that polylactic acid (PLA) and amorphous polyhydroxyalkanoate (PHA) were mixed in a weight ratio of 95:5. A biaxially stretched film was produced.
[0348] (Examples 1-3) As shown in Table 1 below, in the final biaxially stretched film, the same procedure as in Example 1-1 was carried out, except that polylactic acid (PLA) and amorphous polyhydroxyalkanoate (PHA) were mixed in a weight ratio of 90:10. A biaxially stretched film was produced.
[0349] (Examples 1 to 4) As shown in Table 1 below, in the final biaxially stretched film, the same procedure as in Example 1-1 was carried out, except that polylactic acid (PLA) and amorphous polyhydroxyalkanoate (PHA) were mixed in a weight ratio of 80:20. A biaxially stretched film was produced.
[0350] (Examples 1 to 5) A biaxially stretched film was produced in the same manner as in Example 1-3, except that a crystalline polyhydroxyalkanoate (PHA) resin (CJ Co., Korea) was used instead of the amorphous polyhydroxyalkanoate (PHA).
[0351] (Comparative Example 1-1) As shown in Table 1 below, a biaxially stretched film was produced in the same manner as in Example 1-1, except that only polylactic acid (PLA) resin was used.
[0352] (Comparative Example 1-2) A biaxially stretched film was produced in the same manner as in Example 1-1, except that the weight ratio of polylactic acid (PLA) resin and amorphous polyhydroxyalkanoate (PHA) resin in the biaxially stretched film was 70:30, as shown in Table 1 below.
[0353] (Comparative Example 1-3) A mixed resin of polylactic acid (PLA) and amorphous polyhydroxyalkanoate (PHA) similar to that in Example 1-3 was melt-extruded through an extruder at a temperature of 220°C, and then adhered to a cooling roll cooled to 20°C to obtain a sheet. The sheet was then stretched three times in the machine direction (MD), and the stretched sheet was heat-set at 150°C in the heat treatment section of a tenter to produce a uniaxially stretched film.
[0354] [Table 1]
[0355] [Laminate manufacturing] (Example 2-1) -Step 1: Preparing the first resin and the second resin- <First resin> A first polylactic acid (PLA) resin (NatureWorks LLC, 4032D) which is a random copolymer of L-lactic acid and D-lactic acid (L-lactic acid content: 98% by weight), has a weight average molecular weight of about 190,000 g / mol, a melting temperature (Tm) of about 160°C, and a glass transition temperature (Tg) of about 58°C, was mixed with an amorphous polyhydroxyalkanoate (PHA) resin (CJ, Korea) which has a glass transition temperature (Tg) of about -30°C, and silica (Fuji Silysia Chemical, 3.9 μm) to produce a mixed resin. In this case, the first polylactic acid (PLA) and the amorphous polyhydroxyalkanoate (PHA) were mixed so that the weight ratio of the first polylactic acid (PLA) and the amorphous polyhydroxyalkanoate (PHA) in the final first layer was approximately 97:3, as shown in Table 2 below, and the silica content was approximately 500 ppm based on the total weight of the first layer.
[0356] <Second resin> A second polylactic acid (PLA) resin (NatureWorks LLC, 4060D) was prepared, which is a random copolymer of L-lactic acid and D-lactic acid and has a glass transition temperature (Tg) of about 52° C. In this case, the L-lactic acid and D-lactic acid were mixed so that the weight ratio of poly-L-lactic acid (L-PLA) to poly-D-lactic acid (D-PLA) in the final second layer was about 90:10, as shown in Table 2 below.
[0357] -Step 2: Melt co-extrusion to obtain a two-layer laminated sheet- The first resin and the second resin obtained in step 1 were each dried at about 50°C for about 5 hours using a dehumidifying dryer to remove moisture, and then melt-extruded through a single extruder to obtain a two-layer laminated sheet. In this case, the extrusion temperature of the first resin was about 210°C, and the extrusion temperature of the second resin was about 220°C.
[0358] -Step 3: Biaxially stretching and heat setting to obtain a laminate- The laminated sheet obtained in step 2 was stretched about 3 times in the machine direction (MD) at about 75°C, stretched about 3.8 times in the transverse direction (TD) at about 85°C, heat-set at about 140°C, and then relaxed by about 2% to produce a laminate having a thickness of about 19.98 μm.
[0359] (Examples 2-2 to 2-4 and 2-6) As shown in Table 2 below, in step 1 of Example 2-1, except that the compositions of the final first layer and second layer were different, the same procedure as in Example 2-1 was carried out to produce a laminate.
[0360] (Examples 2-5) As shown in Table 2 below, a laminate was manufactured in the same manner as in Example 2-3, except that in step 1 of Example 2-3, crystalline polyhydroxyalkanoate (PHA) resin (CJ Co., Korea) was used instead of amorphous polyhydroxyalkanoate (PHA) and the composition of the final second layer was changed.
[0361] (Comparative Example 2-1) As shown in Table 2 below, a laminate was manufactured in the same manner as in Example 2-1, except that in step 1 of Example 2-1, only the first polylactic acid (PLA) resin was used as the component of the first layer.
[0362] (Comparative Example 2-2) As shown in Table 2 below, in step 1 of Example 2-1, except that the compositions of the final first layer and second layer were different, the same procedure as in Example 2-1 was carried out to produce a laminate.
[0363] (Comparative Example 2-3) As shown in Table 2 below, in step 1 of Example 2-1, a laminate was produced in the same manner as in Example 2-3, except that polytriethylene terephthalate (PTT) was used for the second layer instead of the random copolymer of L-lactic acid and D-lactic acid.
[0364] [Table 2]
[0365] (Evaluation example) (Evaluation Example 1: Thickness and Standard Deviation) The thickness of each of the films and laminates produced in the Examples and Comparative Examples was measured over the entire width, and the thickness deviation was calculated.
[0366] For the biaxially stretched films produced in Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-3, the thickness d (nm) of the film was measured at 5 cm intervals in the width direction using an electric micrometer (Millitron 1245D, FineLeaf Co., Ltd.), and the thickness deviation was calculated according to the following Equation 3.
[0367] Meanwhile, for the laminates manufactured in Examples 2-1 to 2-6 and Comparative Examples 2-1 to 2-3, the thickness d (nm) of the laminate was measured at 5 cm intervals in the width direction using an electric micrometer (Millitron 1245D, FineLeuf Co., Ltd.), and the thickness deviation was calculated using the following Equation 3.
[0368] <Expression 3> Thickness deviation = Maximum thickness in width direction - Minimum thickness in width direction
[0369] (Evaluation Example 2: Tensile strength) Film and laminate test pieces were prepared based on ASTM D882, cut to a length of 100 mm and a width of 15 mm, and attached so that the chuck distance was 50 mm. The test pieces were evaluated based on ASTM D882 using an Instron universal testing machine (UTM, model name 5966) at a tensile speed of 200 mm / min at room temperature of 25°C, and then measured using a program built into the machine.
[0370] TS MD is the tensile strength in the machine direction of the biaxially oriented film or laminate specimen, and TS TD is the transverse tensile strength of the biaxially oriented film or laminate specimen.
[0371] (Evaluation Example 3: Modulus) Based on ASTM D882, biaxially stretched film test pieces and laminate test pieces manufactured in the examples and comparative examples were prepared, and then cut to a length of 100 mm and a width of 15 mm. The test pieces were attached so that the chuck distance was 50 mm. Tests were then conducted using an Instron universal testing machine (UTM, model 5966) at a tensile speed of 200 mm / min. The modulus (kgf / mm) was calculated using a program built into the machine. 2 ) value was obtained.
[0372] The biaxially stretched film test pieces or laminate test pieces were each measured for modulus in the machine direction (MD) and modulus in the transverse direction (TD).
[0373] (Evaluation Example 4: Heat shrinkage rate) Each of the films and laminates prepared in the Examples and Comparative Examples was cut into a length of 150 mm and a width of 1.5 cm regardless of the direction to prepare a test piece. The initial length at room temperature and the length of the biaxially stretched film test piece or laminate test piece immediately after being retained in a hot air oven at 100°C for 5 minutes were measured, and the thermal shrinkage was evaluated by calculating according to the following Equations 1-2 and 2-2, respectively.
[0374] <Formula 1-2> Heat shrinkage rate (S 100)={(L 25 -L 100 ) / L 25}×100 In the above formula 1-2, L 25 is the initial length (mm) of the biaxially stretched film specimen at 25°C, L 100 is the length (mm) of a biaxially stretched film test piece measured immediately after being held in a hot air blower at 100°C for 5 minutes.
[0375] <Formula 2-2> Heat shrinkage rate (S 100 )={(L 25 -L 100 ) / L 25}×100 In the above formula 2-2, L 25 is the initial length (mm) of the laminate test piece at 25°C, L 100 is the length (mm) of a laminate test piece measured immediately after being held in a hot air blower at 100° C. for 5 minutes.
[0376] S MD100 is the thermal shrinkage in the machine direction of the biaxially stretched film or laminate specimen, and S TD100 is the transverse heat shrinkage of the biaxially oriented film or laminate specimen.
[0377] (Evaluation Example 5: Haze and Light Transmittance) The biaxially stretched films and laminates produced in the examples and comparative examples were analyzed for haze and light transmittance using a haze meter (Haze Guard i, BYK-Gardner) according to ASTM D1003.
[0378] (Evaluation example 6: Noise level) In the case of biaxially stretched film, a class 2 sound level meter or higher (hearing weighting circuit: A-weighting, dynamic characteristics: fast mode) as specified by KS C IEC61672-1 was aimed toward the noise source, and the maximum sound level was measured once when a biaxially stretched film test piece 21 cm wide and 29.5 cm long was swung at a speed of 120 times per minute at a point 1.2 to 1.5 m above the ground (if there is an obstacle over 1.5 m high at the measurement point, the point was 1.0 to 3.5 m away from the obstacle toward the noise source). The sound level was measured five times in the same manner to obtain the average sound level (dB).
[0379] On the other hand, for the laminate, a class 2 sound level meter or higher (A-weighting circuit: A-weighting, dynamic characteristics: fast mode) as specified in KS C IEC61672-1 was pointed toward the noise source, and a laminate test piece 21 cm wide and 29.5 cm long was repeatedly crumpled and unfolded 10 times for 10 seconds at a point 1.2 m to 1.5 m above the ground (if there is an obstacle over 1.5 m high at the measurement point, the point was 1.0 m to 3.5 m away from the obstacle in the direction of the noise source), and the maximum sound level was measured once. The sound level was measured five times in the same manner to obtain the average sound level (dB).
[0380] (Evaluation example 7: Loop stiffness) The loop stiffness was measured based on ASTM D747 by fixing a loop-shaped biaxially stretched film test piece and a loop-shaped laminate test piece having a width of 1.5 cm and a length of 18 cm to a loop stiffness tester (Toyo Seiki Seisakusho) and measuring the load at the center of the loop.
[0381] LS MD is the longitudinal loop stiffness of the biaxially oriented film or laminate specimen, and LS TD is the transverse loop stiffness of the biaxially oriented film or laminate specimen.
[0382] (Evaluation Example 8: Flexible Noise Composite Index (LSN)) Using the noise levels and loop stiffnesses of Evaluation Examples 6 and 7, the flexible noise composite index (LSN) of the biaxially stretched film was calculated, which is represented by the following formula 1-1.
[0383] <Formula 1-1> Flexible noise composite index (LSN) = N AVG ×LS In the above formula 1-1, N AVG is the average sound level (dB) calculated by measuring the maximum sound level five times when a class 2 sound level meter specified in KS C IEC61672-1 is aimed toward the noise source and a biaxially stretched film test piece with a width of 21 cm and a length of 29.5 cm is swung at a speed of 120 times per minute at a point 1.2m to 1.5m above the ground. The unit is omitted. The LS is a loop stiffness (gf) measured based on ASTM D747 by fixing a loop-shaped biaxially stretched film specimen having a width of 1.5 cm and a length of 18 cm to a loop stiffness tester and measuring the load at the center of the loop, and is a unit-free value.
[0384] LSN MD is the longitudinal flexibility noise composite index of biaxially oriented film, and LSN TD is the transverse flexibility noise composite index of the biaxially oriented film.
[0385] On the other hand, the noise intensity and loop stiffness of the evaluation examples 6 and 7 were used to determine the composite flexibility noise index (LSN) of the laminate, which is represented by the following formula 2-1.
[0386] <Formula 2-1> Flexible noise composite index (LSN) = N AVG ×LS In the above formula 2-1, N AVGis the average sound level (dB) calculated by measuring the maximum sound level 5 times for each test piece of laminated material with a width of 21 cm and a length of 29.5 cm at a height of 1.2m to 1.5m from the ground, with a class 2 sound level meter as specified in KS C IEC61672-1 facing the direction of the noise source, and repeatedly crumpling and unfolding the piece 10 times for 10 seconds. The unit-free value is the average sound level (dB) calculated by measuring the maximum sound level 5 times for each test piece of laminated material with a width of 21 cm and a length of 29.5 cm. The LS is a loop stiffness (gf) measured based on ASTM D747 by fixing a loop-shaped laminate test piece having a width of 1.5 cm and a length of 18 cm to a loop stiffness tester and measuring the load at the center of the loop, and is a numerical value without a unit.
[0387] LSN MD is the longitudinal flexibility noise composite index of the laminate, LSN TD is the laminate's transverse flexibility noise composite index.
[0388] (Evaluation Example 9: Forming Index) Using the tensile strengths and loop rigidities of Evaluation Examples 2 and 7, the forming index (FI) of the biaxially stretched film and laminate, respectively, represented by the following formulas 1-3 and 2-3, was calculated.
[0389] <Formula 1-3> Forming index (FI)=TS / LS In the above formula 1-3, A biaxially stretched film test piece was prepared according to ASTM D882, cut to a length of 100 mm and a width of 15 mm, and attached so that the chuck distance was 50 mm. The test piece was then measured using a universal testing machine (UTM) for tensile strength (kgf / mm2) without units. TS is a numerical value, and LS is as defined above.
[0390] <Formula 2-3> Forming index (FI)=TS / LS In the above formula 2-3, TS was measured by cutting a laminate test piece into a length of approximately 100 mm and a width of 15 mm according to ASTM D882, attaching the test piece so that the chuck distance was 50 mm, and measuring the tensile strength (kgf / mm 2 ) without units, and LS is as defined above.
[0391] FI MD is the forming index in the machine direction of the biaxially stretched film or laminate specimen, and FI TD is the transverse forming index for the biaxially oriented film or laminate specimen.
[0392] [Table 3]
[0393] As can be seen from Table 3, the biaxially stretched films of the examples containing polylactic acid (PLA) and polyhydroxyalkanoate (PHA) in a specific content range and having a composite flexible noise index (LSN) of 20 or less had excellent strength and flexibility, as well as excellent thermal properties and improved noise levels.
[0394] Specifically, the biaxially stretched films of Examples 1-1 to 1-5 have a tensile strength of 9 to 25 kgf / mm 2 The material has an appropriate range of elasticity and excellent flexibility with a loop stiffness of 0.1 to 0.23 gf. In addition, the noise level is low at 86 dB or less, and the thermal shrinkage rate is extremely low at 15% or less even at a high temperature of 100°C, so both the mechanical properties and thermal characteristics are excellent.
[0395] On the other hand, in the case of the biaxially stretched film of Comparative Example 1-1, which does not contain polyhydroxyalkanoate (PHA), the flexibility noise composite index exceeded 20, so the loop stiffness of the film increased, flexibility decreased, and noise level increased. In particular, it was confirmed that the loop stiffness increased by more than 60% and the noise level increased by more than 10% compared to the biaxially stretched film of Example 1-4.
[0396] On the other hand, in the case of the biaxially stretched film of Comparative Example 1-2, which contains an excess of 30% by weight or more of polyhydroxyalkanoate (PHA), the tensile strength is about 4 to 6 kgf / mm 2 At a high temperature of 100°C, the heat shrinkage rate increased significantly to 17-20%. In addition, the haze increased to over 14%, and the light transmittance was approximately 85%, showing a significant decrease in optical properties.
[0397] Furthermore, in the case of the uniaxially stretched film of Comparative Example 1-3, the thickness deviation was 11.3 μm, an increase of more than 250%, compared to the biaxially stretched film of Example 1-3 containing the same content of amorphous polyhydroxyalkanoate (PHA), the strength in the unstretched transverse direction (TD) was significantly reduced, and the thermal shrinkage rate was increased by more than 40%.
[0398] On the other hand, the biaxially stretched films of Examples 1-1 to 1-4 containing amorphous polyhydroxyalkanoate (PHA) had a low haze of 6.8% or less and excellent light transmittance of 90% or more, whereas the biaxially stretched film of Example 1-5 using crystalline polyhydroxyalkanoate (PHA) had increased haze and decreased light transmittance, resulting in deteriorated optical properties, compared to the biaxially stretched film of Example 1-3 containing the same amount of polyhydroxyalkanoate (PHA).
[0399] [Table 4]
[0400] As can be seen from Table 4, the laminate of the embodiment, which includes a first layer containing a first polylactic acid (PLA) and a polyhydroxyalkanoate (PHA) in a specific content range and a second layer containing a second polylactic acid (PLA), had excellent strength and flexibility at the same time, excellent thermal properties, improved noise levels, and excellent interlayer adhesion properties due to good interlayer compatibility between the first and second layers.
[0401] Specifically, the laminates of Examples 2-1 to 2-6 have a low noise level of 86 dB or less, a loop stiffness of 0.1 to 0.2 gf, and excellent flexibility. MD ) is 7-14kgf / mm 2 When the film satisfies the appropriate range, the heat shrinkage rate is extremely low at 15% or less even at a high temperature of 100°C, the haze is 10% or less, and the light transmittance is 90% or more, so that the mechanical properties, thermal properties, and optical properties are all excellent.
[0402] On the other hand, in the case of the laminate of Comparative Example 2-1, which does not contain polyhydroxyalkanoate (PHA) in the first layer, the loop rigidity of the laminate increased, its flexibility decreased, and its noise level increased. In particular, it was confirmed that the loop rigidity and noise level increased compared to the laminate of Example 2-1, which has the same composition of the second layer.
[0403] On the other hand, in the case of the laminate of Comparative Example 2-2 in which the first layer contained an excessive amount of polyhydroxyalkanoate (PHA) of 30% by weight or more, the thickness deviation of the laminate increased and the longitudinal tensile strength (TS MD ) and transverse tensile strength (TS TD ) are approximately 6.4kgf / mm 2 and 7.8 kgf / mm 2 At a high temperature of 100°C, the heat shrinkage rate increased significantly to 15.3 to 16.8%, and the optical properties also decreased.
[0404] Furthermore, in the case of the laminate of Comparative Example 2-3 in which polytriethylene terephthalate (PTT) was used instead of the second polylactic acid in the second layer, the compatibility between the first and second layers was insufficient during stretching, resulting in insufficient interlayer adhesion properties, and delamination made it impossible to produce a stretched film.
[0405] In contrast, the laminating agents of Examples 2-1 to 2-6 are composed of a first layer containing a first polylactic acid (PLA) and a polyhydroxyalkanoate (PHA) and a second layer containing a second polylactic acid (PLA) disposed on one side of the first layer, and therefore have good compatibility, resulting in excellent adhesive properties for the first and second layers even after stretching.
[0406] On the other hand, in the case of the laminate of Example 2-5 using crystalline polyhydroxyalkanoate (PHA), the thermal shrinkage rate was significantly reduced compared to the laminates of Comparative Examples 2-1 to 2-3, and drying for extrusion processing in the process was easy and there was less bubble generation during extrusion processing. However, the modulus and noise level were slightly increased compared to the laminates of Examples 2-1 to 2-4 which contained amorphous polyhydroxyalkanoate (PHA) in the first layer.
[0407] Furthermore, in the case of the laminate of Example 2-6 in which the weight ratio of L-PLA and D-PLA in the second layer was increased to 62:38, the mechanical properties, thermal properties, optical properties, noise level, flexibility, etc. were improved compared to the laminates of Comparative Examples 2-1 to 2-3, but the thickness deviation of the laminate increased relatively and the heat shrinkage rate increased compared to the laminate of Example 2-3 in which the composition of the first layer was the same. Also, it was confirmed that the processability and productivity were somewhat reduced due to insufficient winding properties during film production and processing. [Explanation of symbols]
[0408] 1: Laminate 11:Second layer 12: 1st layer 13: Corona layer 14: Coating layer
Claims
1. a first layer comprising a first polylactic acid (PLA) and a polyhydroxyalkanoate (PHA); a second layer disposed on one side of the first layer and including a second polylactic acid (PLA); A laminate, wherein the first layer comprises greater than 0% and less than 30% by weight of polyhydroxyalkanoate (PHA), based on the total weight of the first layer.
2. The polyhydroxyalkanoate (PHA) is a copolymerized polyhydroxyalkanoate (PHA), The laminate according to claim 1, wherein the copolymerized polyhydroxyalkanoate (PHA) contains at least one unit represented by the following chemical formula 1 and at least one unit represented by the following chemical formula 2: [Chemical formula 1] In the above Chemical Formula 1, The R 1 is the substituted C 1 ~C 8 is an alkylene of the formula: m is an integer of 1 or more, [Chemical formula 2] In the above Chemical Formula 2, The R 2 is a substituted or unsubstituted C 1 ~C 8 is an alkylene of the formula: n is an integer of 1 or more.
3. The laminate according to claim 2, wherein the copolymerized polyhydroxyalkanoate (PHA) contains the unit of Chemical Formula 2 in an amount of 1% by weight to 60% by weight based on the total weight of the copolymerized polyhydroxyalkanoate (PHA).
4. the second layer comprises a mixture of L- and D-isomers of the second polylactic acid; 2. The laminate of claim 1, wherein the second layer comprises 5% to 30% by weight of the D-isomer, based on the total weight of the second polylactic acid.
5. further comprising a corona layer, a coating layer, or both, disposed on the other side of the first layer; the corona layer is formed by corona treatment of the first layer and contains polar functional groups selected from the group consisting of -CO, -COOH, and -OH; the first layer has a surface tension of 38 dyn / cm or more relative to the corona-treated surface; The coating layer includes a primer coating layer, 2. The laminate according to claim 1, wherein the primer coating layer is formed on the other surface of the first layer or the other surface of the corona layer by primer treatment, and has a surface resistance of 0.1 to 30 Ω / □.
6. The tensile strength (TS) of the laminate in the machine direction (MD) MD ) is 7 to 14 kgf / mm 2 , and the tensile strength in the transverse direction (TD) (TS TD ) is 8 to 20 kgf / mm 2 and The thermal adhesive strength of the first layer and the second layer is 0.7 to 2.0 kgf / mm 2 The laminate according to claim 1 ,
7. Providing a first resin including a first polylactic acid (PLA) and a polyhydroxyalkanoate (PHA) and a second resin including a second polylactic acid (PLA) (Step 1); Step 2: melt-co-extruding the first resin and the second resin to obtain a two-layer laminated sheet; and (3) biaxially stretching and heat setting the laminated sheets to obtain a laminate. The laminate includes a first layer including a first polylactic acid (PLA) and a polyhydroxyalkanoate (PHA); a second layer disposed on one side of the first layer and including a second polylactic acid (PLA); A method for producing a laminate, wherein the first layer comprises greater than 0 weight % and less than 30 weight % of polyhydroxyalkanoate (PHA), based on the total weight of the first layer.
Citation Information
Patent Citations
Polyhydroxyalkanoate copolymer and polylactic acid compositions for laminates and films
JP2004536897A
Biodegradable synthetic paper and its manufacturing process
JP2005306932A
Biodegradable advertising material and method for producing the same
JP2012512053A
Environmentally friendly high-strength resin composite material
JP2015517935A
Laminate, coffee capsule, food container, and cosmetic container
JP2019181877A